Long-term nutrient enrichment constrains root exudate-induced priming effects across soil depths in a subtropical forest - Jing Zhou; Jie Li; Na Qiao; Guang Zhao; Xingliang Xu (Applied Soil Ecology, 2026)

An ER-targeted electronic-switched cascade probe for synchronous dual-channel imaging of H2S and HClO during liver fibrosis - Jiaxue Yang; Yi Le; Na Wang; Beibei Wu; Yuyang Song; Ting Wang; Birong Yang; Fan Zhou; Li Liu (Analytica Chimica Acta, 2026)

Fe(II)-driven abiotic-biotic relay alleviates denitrification bottleneck via chemical nitrite reduction and intracellular carbon - Na Hu; Qi Feng; Chenxi Li; Yuanyuan Liu; Baoli Zhu; Tianci Guo; Lei Tong; Jianbo Shi; Robert A. Sanford; Shuyi Li; Yu He; Yidan Hu; et al. (Water Research, 2026)

Intranasal BCG cell wall polysaccharide-based subunit vaccine confers protection against Mycobacterium bovis challenge in mice - Na Li; Mengting Zhou; Yinjuan Song; Li Tang; Hui Ma; Jian Xu; Jian Cao; Na Li; Yuefeng Chu (Veterinary Microbiology, 2026)

Regulation of mycelium–egg white protein composite formation by pH and ionic strength - Mukadaisi Muhedaner; Ziqing Song; Na Huang; Mengjun Li; Guanghong Zhou; Keping Ye (Food Bioscience, 2026)

Regulatory mechanisms of N2O emissions from latosolic red soil by different ecotypes of earthworms: Insights from microbial diversity and metagenomic analysis - Chang Wei; Chang-Wen Yun; Xiao-Qing Li; Lang-Hao Lai; Jian-Peng Gao; Meng-Ping Tang; Chun-Na Zhou; Yu-Long Zhang; Hui-Juan Xu (Environmental Pollution, 2026)

The dynamic complexity of critical mineral supply chains reveals the paradox of energy transition - Junhui Li; Yongguang Zhu; Shiquan Dou; Qian Zhang; Saleem H. Ali; Gang Liu; Yanqiong Zhao; Na Zhou; Jinhua Cheng; Deyi Xu (Ecological Economics, 2026)

Photodegradation process of microplastics mediated by biochar-derived dissolved organic matter: Insights from density functional theory calculations - Kunliang Jiang; Zaifeng Wang; Huacheng Xu; Zhaoliang Peng; Yuxuan Zhang; Wenkang Li; Shengkai Zhou; Qingru Wan; Na Song (Chemical Engineering Journal, 2026)

A triboelectric sensor array based on facial muscle-action unit-emotion mapping toward astronaut psychological monitoring in long-term missions - Xuyan Hou; Huiyuan Jing; Meiyang Zhang; Fengyan Liu; Ruiwen Zhao; Zhonglai Na; Pingting Zhao; Yuhui Liu; Ximing Zhao; Linbo Xin; Jian Zhou; Xi Chen; et al. (Chemical Engineering Journal, 2026)

A heparan-like glycosaminoglycan from the white jade snail: Precise structural elucidation, alkaline-induced artificial changes, and non-anticoagulant heparanase inhibition - Pin Wang; Na Gao; Qijiang Mao; Lutan Zhou; Yu Wang; Ying Pan; Fengyun Wu; Penghao Kang; Zanyang Min; Yujun Ma; Huifang Sun; Xiang Shi; et al. (Carbohydrate Polymers, 2026)

Corrigendum to “Fermented Chinese herbal medicines combined with probiotics promote growth of fattening lambs under heat stress by modulating rumen mucosal barrier functions” [Anim. Feed Sci. Technol. 326 (2025) 116384] - Shoupei Zhao; Xinsheng Sun; Na Zhao; Hongwei Zhang; Gaofu Wang; Lu Zhang; Yuqing Liu; Haitong Yang; Jianjie Li; Jia Zhou; Yuhong Gao (Animal Feed Science and Technology, 2026)

Pomegranate Peel Polyphenols-incorporated PVA/CMC Hydrogels for High-efficiency Removal of Methylene Blue from Aqueous Solutions - Qihua Zhou; Chenyang Wang; Simin Xu; Ziyi Duan; Tiantian Fu; Zhonghai Ding; Na Li (Water, Air, & Soil Pollution, 2026)

Cadmium stress restructures bacterial communities but induces limited variation in predicted functional profiles in the rhizosphere of Sedum plumbizincicola: implications for Cd phytoremediation - Yanan Cheng; Jing Jiang; Shangqi Xu; Meng Na; Xiaoping Li; Jihai Zhou (Rhizosphere, 2026)

Microbial aerobic degradation of 4-isopropylnitrobenzene by Sphingobium yanoikuyae strain SG1 - Na Yang; Isabelle Camara; Sharmin Afroz; Natanna Melo; Savia Gavazza; Blake G. Lindner; Konstantinos T. Konstantinidis; Tao Li; Jim C. Spain; Ning-Yi Zhou (Journal of Hazardous Materials, 2026)

Outdoor light at night exposure and hypertension risk in adults: A longitudinal cohort study from the FLORA project - Shuo Zhang; Xiao-Fan Lu; Muhammad Amjad; Lin-Jing Gong; Na Liu; Hong-Xing Zou; Xiao-Yi Liu; Le-Bing Wang; Yuan-Yuan Fan; Yang-Yang Li; Yi-Ran Chen; Wen-Wen Bao; et al. (Environmental Research, 2026)

Effects of functional fermented feed on growth performance, physiological functions, and gut microbiota of Penaeus vannamei - Xin Yu; Na Li; Yulong Zhou; Teng Li; Zeyan Xi; Liwen Liao; Luqing Pan (Animal Feed Science and Technology, 2026)

Differential priming effects induced by leaf- and root-litter in subtropical Chinese fir soil - Jing Zhou; Jie Li; Na Qiao; Guang Zhao; Xingliang Xu (Plant and Soil, 2026)

Dietary Bacillus sp. ‌Modulates Multi-tissue Metabolism Through Gut Microbiota Remodeling in High-fat Fed Larimichthys crocea - Ruojing Li; Biao Yuan; Xin Yi; Ermei Yin; Bi Huang; Qianwen Min; Jiayu Zhou; Meiqi Lv; Bo Zhang; Na Zhao (Probiotics and Antimicrobial Proteins, 2026)

Freeze-thaw perturbation decreases priming of soil organic carbon mineralization induced by straw return in croplands - Meng Na; Mengqin Xiang; Yifan Wang; Haifeng Lu; Jihai Zhou; Chunjie Tian; Lu-Jun Li; Yuqing Miao; Hailong Sun; Shangqi Xu; Johannes Rousk (Soil Biology and Biochemistry, 2026)

The cytokinin oxidase/dehydrogenase MdCKX4 regulates drought tolerance in Malus domestica - Tong Li; Yu-Feng Zhang; Joy Xin-Yue Zhai; Zi-Quan Feng; Shuo Ma; Xin-Yi Li; Huai-Na Gao; Long-Xin Luo; Zhi Li; Qi Zhang; Min-Min Zhou; Ya-Li Zhang; et al. (Plant Science, 2026)

Identifying driving factors of lacustrine groundwater discharge in Lake Taihu with integrated surface-subsurface numerical modeling - Hao Zhou; Yadong Shi; Yue Zou; Ya Jiang; Na Zheng; Subin Cheng; Donghao Wu; Xin Luo; Chaomeng Dai; Juntao Zheng; Zhi Li (Journal of Hydrology, 2026)

Socioeconomic drivers of riverine biochemical oxygen demand: Insights from interpretable machine learning - Na Huang; Dawei Wang; Penghui Li; Lin Chen; Wei Wang; Zeng Zhou; Pei Xu; Sile Li; Yali Zhang; Yilan Jiang (Journal of Environmental Management, 2026)

Associations between prenatal exposure to indoor air pollution and ambient particulate matter with infant growth - Jinlang Lyu; Tiantian Li; Shuang Zhou; Xin Yuan; Zheng Bao; Na Han; Gongbo Chen; Yuelong Ji; Qin Li; Jue Liu; Hui Wang; Jianlin Hu; et al. (Journal of Environmental Sciences, 2026)

Deciphering drought resistance in tetraploid Passiflora edulis by integrated transcriptomic and metabolomic profiling - Xin Su; Chiyu Zhou; Sunling Li; Jianzhen Liao; Xiaoyue Zhang; Na Li; Xuesha Gu; Nianhui Cai; Yulan Xu (Food Bioscience, 2026)

Conductive nanofiber veils: Their preparation and application to effectively increase through-thickness electrical conductivity and interlaminar toughness of epoxy CFRPs - Yan Li; Gang Zhou; Na Ning; Lei Chen; Zhengyan Guo; Yi Wei (Chemical Engineering Journal, 2026)

Survey on Dioxin Contamination in Chinese-Produced Pesticides and Evaluation of Dioxin Emissions During their Application - Wei Xie; Ya-chen Zhou; Bin Fang; Hui-li Ma; Na Li; Shu-qi Zhang (Water, Air, & Soil Pollution, 2026)

Combined toxicity and mechanism of cadmium and neonicotinoid insecticide to rice (Oryza sativa L.): reduced antioxidant defence mediated by flavonoid - Zhaoxia Fan; Na Liu; Fei Ge; Feng Li; Wenjun Zhou; Juan Gao (ENGINEERING Environment, 2026)

Study on the engineering characterization of stabilized cadmium-contaminated soil using MgO activated FA and GGBS - Cuihong Li; Yubo Zhou; Wei Wang; Shaoyun Pu; Na Li; Ping Jiang (Bulletin of Engineering Geology and the Environment, 2026)

Multi-phase and Multi-mode Gait Recognition with Few Channels and Few Features Based on the Fusion of sEMG and Acceleration - Songbo Zhou; Chaoming Luo; Xinyi Ma; Yongxin Lv; Na Ta; Junfeng Gao; Zhengyi Li; Dandan Yang; Hui Zhou (Annals of Biomedical Engineering, 2026)

Chronic intermittent hypoxia sustains the low-grade inflammatory memory of monocytes via activation of myelopoiesis - Shi Qi Li; Yi Wang; Meng Yao Li; Liu Zhang; Xi Xi Chen; Ying Ni Lin; Li Na Zhou; Xian Wen Sun; Yong Jie Ding; Qing Yun Li (Inflammation Research, 2026)

From morphological constraints to genomic SNPs: Developing population identification methods exemplified by large yellow croaker (Larimichthys crocea) - Zebin Zhou; Xubing Ba; Qianwen Min; Jiayu Zhou; Xin Yi; Ruojing Li; Bi Huang; Na Zhao; Bo Zhang; Songlin Chen (Aquaculture, 2026)

Curcumol induces autophagy-dependent hepatic stellate cell death through methionine metabolism disruption - Yi-jie Gao; Ya Zhou; Yi-ning Li; Kai-yao Yang; Si-wei Xia; Meng-ru Hu; Yang Li; Li Chen; Fei-xia Wang; Shuai Lu; Na-qi Lian; Shi-zhong Zheng; et al. (Toxicology and Applied Pharmacology, 2026)

Arabidopsis MPK2 negatively regulates drought tolerance by balancing growth and stress responses - Yuzhen Li; Yi Feng; Na Li; Jisheng Li; Heng Zhou; Linfei Liu (Plant Science, 2026)

Expanded coverage of N-acyl amino acids using one-pot micro synthesis-chemical derivatization-LC-MS strategy: A key to bioactive compounds analysis in fermented soybean - Jie Han; Yujie Li; Lanjia Ao; Li Zhang; Tingting Zhou; Na Li; Jian-Lin Wu (Food Chemistry, 2026)

Daily mortality prediction under compound environmental stressors: Comparing epidemiological time series models and machine learning models - Wanjie Wang; Xiaoyan Zhou; Na Li; Feng Chen; Jingqiao Fu; Zhiyang Su; Yuqing Yao; Xiaoyan Yuan; Sirui Lin; Mengfan Chen; Maji Gan; Jieming Zhong; et al. (Environmental Research, 2026)

Self-assembling gardenia pectin gel for cholestatic liver injury: Dual mechanisms of hepatoprotection via PPARα activation and gut microbial modulation - Lanjia Ao; Yujie Li; Lingling Zheng; Xiaolin Chen; Haoyuan Zeng; Wen Miao; Shuxian Yang; Tingting Zhou; Na Li; Jian-Lin Wu (Carbohydrate Polymers, 2026)

The EAL domain protein YjcC contributes to the pathogenicity of Pseudomonas plecoglossicida - Li Cao; Yuanyuan Zhou; Na Guo; Chengqi Xiong; Qionglin Liu; Xiaoyue Dang; Ruoyu Liu; Xiang-Yang Zhang; Xinhua Chen (Aquaculture International, 2026)

Secondary chlorination enhanced the role of pipe materials in shaping chlorine-resistant microbiome and antibiotic resistome in secondary water supply systems - Yuanrong Qiu; Yanling Yang; Na Li; Xing Li; Zedong Lu; Zhiwei Zhou; Sha Feng; Yongwang Liu (Journal of Hazardous Materials, 2026)

Syngas production from biomass at low temperatures through dual waste valorization with metal-promoted phosphogypsum - Sheng Qian; Kaihong Wen; Wei Zhang; Chun Zhou; Yingrong Miao; Tiantian Li; Senshen Yu; Xingyong Li; Na Liu; Liping Ma; Longlong Ma; Shijie Liu; et al. (Journal of Environmental Chemical Engineering, 2026)

Plastisphere as an eco-site for horizontal gene transfer: Enhancing antibiotic resistance in marine biofilms - Chaoran Li; Zhihang Chen; Hongyi Chen; Zhonglai Zhou; Lingchen Zhang; Lina Zhao; Hui Zhong; Na Wang (Environmental Research, 2026)

Source contact engineered high-gain and low-power Schottky-barrier transistors for electrophysiological amplification - Biao Zhou; Linjing Wang; Chenchen Wei; Jietao Zhuo; Na Liao; Wei Zhou; Huihua Xu; Fengyu Li; Zhao Dong (Chemical Engineering Journal, 2026)

Andrographolide induces testicular damage by triggering ferroptosis in Sertoli cells via disruption of β-TrCP-mediated ATF4 ubiquitination and degradation - Jiaqi Li; Zhengxin Lu; Nan Zhang; Xiaowei Zhou; Yuanbiao Ma; Jia-qi Li; Yimu Zhang; Zhewen Deng; Na Lin; Peng Yue; Yilin Yang; Qi Zhang; et al. (Chemico-Biological Interactions, 2026)

Regulated cell death: a multidimensional regulatory network in the pathogenesis of renal fibrosis - Wen Li; Liang Zhou; Jinji Zhang; Jingying Sun; Qing Feng; Kunyi Wu; Na Zhu (Apoptosis, 2026)

DICP1-A precisely degrades STING-A but not STING-B to suppress IFN expression through the autophagic pathway in gibel carp - Yue Wu; Shun Li; Fan-Xiang Gao; Zhi Li; Rui-Hai Gan; Can Zhang; Xiao-Li Yang; Zhuo-Cong Li; Chu-Jing Zhou; Yang-Yang Wang; Na Xu; Xue-Bing Wang; et al. (Aquaculture, 2026)

Influence of salinity on the dynamic improving nutritional value of channel catfish (Ictalurus punctatus): Insights from targeted and untargeted metabolomics and antioxidant capacity analysis - Zhen Li; Yali Yu; Quanyou Guo; Na Lin; Xiaorong Lu; Jie Peng; Tao Mao; Yuntao Zhou; Lang Zhang; Liu Fang (Aquaculture, 2026)

Identification of novel genes involved in pediatric congenital heart disease using trio-based whole genome sequencing - Bo Wang; Mo Li; Wei Zhou; Huiwen Chen; Ying Xiang; Guocheng Shi; Guoling You; Luan Chen; Yesheng Zhang; Xiaoqing Zhang; Yunqian Gao; Lulu Li; et al. (Science Bulletin, 2026)

Tumor-associated bacterial effectors: novel frontiers in tumor biology and immunity - Jia-Hao Dai; Ying-Qi Lu; Sen-Yu Feng; Xi-Rong Tan; Li-Li Li; Yue-Can Zeng; Jian-Zhou Chen; Jun Ma; Na Liu (Science Bulletin, 2026)

Unraveling the mass transfer limitations on oxidation pathways in carbon-assisted water electrolysis: a comparative study of self-supporting sacrificial anode and slurry electrolysis systems - Jianming Fan; Jingze Gao; Na Li; Xing Zhou; Yongfeng Zhang (Chemical Engineering Journal, 2026)

Serum Endogenous Opioid Levels are Associated with Self-Injury Severity in Adolescents with Non-Suicidal Self-Injury and Comorbid Depression - Jin-Jun Ding; Xiao-Li Liu; Ang Li; Yi-Yao Liang; Yu-Bo Wang; Xiao-Na Zhu; Jie Li; Jie Weng; Lan Yan; Wen-Wen Duan; Zi-Chen Zhang; Ti-Fei Yuan; et al. (Neuroscience Bulletin, 2026)

Spatiotemporal distribution and host association of antibiotic resistance genes in sediment of Qiantang river basin - Qiannan Jin; Jie Li; Yantan Zhou; Guangqian Zhao; Yuhan Jiang; Na Cheng; Lifang Hu (Environmental Geochemistry and Health, 2026)

The mechanism of Longdan Xiegan pills in chronic stress-induced hypertension:a study based on network pharmacology and experimentalvalidation - Huizhuo Jia; Mingyao Lv; Ying Yang; Zhe Wang; Yanzhao Zhang; Jinxu Zhou; Longfei Xia; Jing Zhang; Haifu Wan; Na Li (In Silico Pharmacology, 2026)

Discovery of anti-glioblastoma natural products based on andrographolide derivatives: efficiently identifying potential multi-target and multifunctional molecules through the integration of in silico methods and experimental verification - Ya-Lin Li; Jun Mao; Xin-Yu Zhou; Duan-Na Zhang; Yu-Zhi Li; Zhi-Xing Cao; Ji-Xia Ren (Molecular Diversity, 2026)

Titanium ion inhibits osteogenic ability of osteoblasts by up-regulating osteoblast Agt gene via macrophages - Mao Shan Wang; Hai Feng Zhou; Huan Li; Li Na Gao; Yao Feng; Hongguang Zhu (Journal of Trace Elements in Medicine and Biology, 2026)

Effects of cadmium-tolerant bacteria combined with biochar on cadmium and selenium dynamics in rice grown on seleniferous soils: Insights from a soil bacterial community analysis - Yanan Cheng; Jing Jiang; Lanping Song; Shangqi Xu; Meng Na; Kun Cheng; Daming Li; Shoubiao Zhou; Jihai Zhou (Journal of Environmental Chemical Engineering, 2026)

Crystal phase-dependent ZrO2 for fluoride adsorption in hydrochloric acid - Qian Wu; Xin Huang; Shiyu Sun; Yan Li; Fengzhen Liu; Xin Chen; Na Wang; Ting Wang; Zijian Zhou; Bin Lu; Hongxun Hao (Journal of Environmental Chemical Engineering, 2026)

Selective depolymerization of lignin into oxygen-containing aromatics by novel RuW/TiO2 catalyst - Xiaolu Wang; Heya Na; Jianxiu Hao; Na Li; Yanpeng Ban; Huacong Zhou; Daqian Ding; Haigang Hao; Quansheng Liu (Journal of Environmental Chemical Engineering, 2026)

Mechanism analysis and application of highly efficient nitrogen-removing strains: Nitrogen-removal characteristics-pathways and optimal inoculum size - Liwen Liao; Zilu Li; Luqing Pan; Zeyan Xi; Teng Li; Na Li; Yulong Zhou (Journal of Environmental Management, 2026)

Soil bacterial adaptation to plant invasion alters stoichiometric imbalances between soil microbes and resources in subtropical ecosystems - Meng Na; Shangqi Xu; Yong He; Tianyi Lu; Xiaoping Li; Jihai Zhou (Plant and Soil, 2026)

Interpretable data-driven modeling of total phosphorus dynamics from 2005 to 2024 in a large shallow lake - Weipeng Lin; Yongqiang Zhou; Ze Ren; Wei Zou; Hongwei Guo; Na Li; Yunlin Zhang; James Elser; R. Iestyn Woolway; Kun Shi; Guangwei Zhu; Boqiang Qin; et al. (Water Research, 2026)

Pore architecture reshaping and microbial network restructuring drive sunflower yield gains in saline-alkali soil via straw-sand interlayer systems - Xiaolong Bai; Na Liu; Jie Zhou; Jiashen Song; Guoli Wang; Aiping Chen; Yongliang Chen; Jing Wang; Hongyuan Zhang; Yuyi Li (Soil and Tillage Research, 2026)

Pressure-driven depolymerization of Antarctic krill aggregates: Structural reconfiguration and gelation-enhanced functionality - Na Li; Qingcheng Meng; Xin Zhao; Fawen Yin; Dayong Zhou; Deyang Li (Food Chemistry, 2026)

Effect of ultrahigh-pressure-driven starch-fatty acid complexes on gel properties of shrimp surimi: Deciphering chain length specificity and multiscale structural modulation - Na Li; Jitao Zhu; Dayong Zhou; Deyang Li (Food Hydrocolloids, 2026)

Construction of nano-rubber toughened double-network hydrogels and the efficient adsorption performance and mechanism for uranyl ions - Bo Tian; Jianwei Zhang; Wenze Li; Jinfeng Li; Na Zhou; Zhigang Li; Wa Gao; Nan Zhang; Hongtao Zhao (Environmental Research, 2026)

Enhancing the photocatalytic membranes performance via lignin sacrificial modification - Qian Wang; Na Zhou; Yuhan Zhang; Hangtian Lu; Xinglin Li; Rong Xu; Zhengzhong Zhou (Chemical Engineering Journal, 2026)

Brain functional basis of the association between positive expectation and acupuncture efficacy in knee osteoarthritis - Ze-Yi Wang; Cun-Zhi Liu; Xiao-Ya Wei; Na Zhang; Jin-Ling Li; Chihkai Lee; Hang Zhou; Jian-Feng Tu; Xu Wang (Brain Imaging and Behavior, 2026)

Increased drought intensity stimulates the extracellular polymeric substance accumulation and their contribution to soil organic carbon rather than microbial necromass - Huijun Li; Baorong Wang; Haoning Chen; Na Li; Yue Zhou; Zhaolong Zhu; Jinshi Jian; Gurpal S. Toor; Shaoshan An (Soil Biology and Biochemistry, 2026)

Synthesis of amidoxime functionalized hydrogel for in-situ toughening and adsorption of uranium - Bo Tian; Jianwei Zhang; Jinfeng Li; Na Zhou; Wenze Li; Wa Gao; Nan Zhang; Hongtao Zhao (Journal of Environmental Chemical Engineering, 2026)

Research on the carbon cycle of surface water-groundwater in the Jianghan Dongting Plain of the Yangtze River Basin, China - Meiyan Hu; Peijiang Zhou; Chao Meng; Xiaobin Li; Xiaoxi Chen; Jingyi Xie; Shengkai Cao; Xiaodi Zhang; Zhen Ni; Guangshui Na (Journal of Contaminant Hydrology, 2026)

Study on mechanical properties of non-diagenetic hydrates-bearing sediments under in-situ static conditions - Na Wei; Jiang Wu; Haitao Li; Jun Pei; Shouwei Zhou; Jinzhou Zhao; Bjørn Kvamme; Richard Banks Coffin; Anping Feng; Jianyong Feng (Fuel, 2026)

Directing CH4 selectivity in CO2 photoreduction with Au nanoparticles electron mediation in Z-scheme WS2/g-C3N4 heterojunctions - Shicheng Liu; Jianghong Zhang; Jing Xiang Ng; Junbo Yu; Qulan Zhou; Na Li; Yanqing Niu (Chemical Engineering Journal, 2026)

Corrigendum to “Non-lytic nanozyme hydrogel for the treatment of fungal keratitis by silent pathogen eradication and host inflammation suppression” [Chem. Eng. J. 527 (2026) 171844/ CEJ_171844] - Na Li; Xia Qi; Li Ma; Xiaoyu Zhang; Yuxin Liu; Shijiu Chen; Fengmei Shan; Qun Wang; Qingjun Zhou; Ting Wang; Hongwei Wang; Weiyun Shi (Chemical Engineering Journal, 2026)

Identification of low-toxicity DNA topoisomerase I inhibitors with potential blood–brain barrier penetrability for glioblastoma therapy: structure-based virtual screening reveals promising novel Scaffolds - Ya-Lin Li; Jun Mao; Zhong Cheng; Xin-Yu Zhou; Duan-Na Zhang; Yu-Zhi Li; Zhi-Xing Cao; Ji-Xia Ren (Molecular Diversity, 2026)

Amino Acid Metabolism-Related Gene Kynureninase (KYNU) as a Prognostic Predictor and Regulator of Diffuse Large B-Cell Lymphoma - Yu Zhang; Shi Feng; Liemei Lv; Cong Wang; Ran Kong; Guangcai Zhong; Na Wang; Peipei Li; Xiangxiang Zhou (Biochemical Genetics, 2026)

Comprehensive analysis of metabolic response in Arabidopsis thaliana under heavy metal stress by mass spectrometry - Zhongyan Zhou; Donghao Li; Na Wang; Xiujuan Hong; Wen Su; Cheng Guo; Chongsheng He; Lei Yue (Journal of Hazardous Materials, 2026)

Non-lytic nanozyme hydrogel for the treatment of fungal keratitis by silent pathogen eradication and host inflammation suppression - Na Li; Xia Qi; Li Ma; Xiaoyu Zhang; Yuxin Liu; Shijiu Chen; Fengmei Shan; Qun Wang; Qingjun Zhou; Ting Wang; Hongwei Wang; Weiyun Shi (Chemical Engineering Journal, 2026)

Structural characterization of fructans from Polygonatum kingianum and their effects on LOP-induced constipation in mice - Na Shen; Xiaodong Zhang; Yue Zhou; Jiawei Li; Bin Qiu; Xuefang Li; Niman Bao; Jie Yu (Carbohydrate Polymers, 2026)

Comprehensive assessment of secondary metabolite diversity and in vitro anti-diabetic properties in Sanghuangporus quercicola cultured under different conditions - Mingxing Yu; Na Zhang; Xiaofeng Ma; Xiaoshuang Zhou; Shude Yang; Weihang Peng; Yin Li; Yuejun Mu; Xianhao Cheng; Rui Zhang; Yongfei Ming (Systems Microbiology and Biomanufacturing, 2026)

Black carbon contamination in urban street dust of Xuzhou: pollution characteristics, magnetic responses and source identification - Yinghong Liu; Xuesong Wang; Lihua Zhou; Na Li (Environmental Geochemistry and Health, 2026)

Sustainable wood waste management: an experimental study on the engineering scale-up application of the two-step steam explosion technology for chips from poplar processing - Fengming Fan; Zhe Li; Na Xiao; Huixue Liu; Qianyi Sheng; Bo Zhou; Zhichao Lei; Huiliang Liu; Yun Yang; Chenxi Xia (Environment, Development and Sustainability, 2025)

Healthy diet and slower biological aging as protective factors against microvascular complications in type 2 diabetes - Han Zhou; Shuai Ben; Qian Ma; RuiKang Yang; Jiao Xia; XiongYi Yang; Jing Li; JunYa Zhu; Qian Liu; Ya Zhao; Na Li; Kun Liu; et al. (GeroScience, 2025)

Nuclear transport factor IPO4 modifies localization by PCV2 and facilitates viral replication - Cui Lin; Chengcheng Wu; Fanfan Zhang; Na Li; Haiqin Li; Lihan Tao; Jia Tan; Yanbing Zeng; Shaopei Fang; Quanyong Zhou (Veterinary Microbiology, 2025)

Spatiotemporal variations in global lake clarity and responses to climate and landscape drivers - Yibo Zhang; Yunlin Zhang; R. Iestyn Woolway; Zhigang Cao; Xiwen Wang; Jian Zhou; Yongqiang Zhou; Weijia Wang; Na Li; Boqiang Qin; Kun Shi (Science Bulletin, 2025)

Structure-based molecular design of fungicidal β-ketonitrile derivatives with biphenyl moiety as novel succinate dehydrogenase inhibitors - Cong Zhou; Ziye Cao; Li Sun; Na Zhai; Liangliang Cheng; Zheyi Feng; Zhong Li; Xuhong Qian; Jiagao Cheng (Pesticide Biochemistry and Physiology, 2025)

EphA/EphrinA5 signaling pathway involved in the abnormal synaptic remodeling and neurotoxicity caused by benzo[a]pyrene - Xin Li; Shuang Zhou; Xiaoling Zhou; Jinfeng Zhang; Na Xia; Yangyang Li; Zhanfei Song; Hongmei Zhang (NeuroToxicology, 2025)

Separation and detection of ginsenosides: Challenges, industrial implications, and developments - Anqi Liu; Junjun Zhou; Yiling Luo; Yingbo Li; Yu Yang; Zibo Meng; Lixia Zhou; Hanlei Zhang; Na Liu; Ming Hui; Dandan Zhai; Peng Li (Food Research International, 2025)

Multidimensional strategy for discovering saltiness-enhancing peptides in shrimp heads integrating ultra-high pressure hydrolysis and machine learning - Na Li; Yafang Song; Yang Liu; Rong Liu; Yahong Li; Dayong Zhou; Deyang Li (Food Chemistry, 2025)

Highly conjugated 2D bimetallic adaptive nanoplatform incorporating self-assembled carbon dots enables visual diagnosis and spatiotemporal management of infected wounds - Na Li; Yi Cao; Wenqing Shi; Hongfu Cao; Chen Zhou; Wen Zou; Linyun Pu; Jie Liang; Qiguang Wang; Yujiang Fan; Xingdong Zhang (Chemical Engineering Journal, 2025)

Elucidation of the biodegradation pathways of polyurethane and polyethylene terephthalate by a Fusarium strain enriched from soil-plant systems - Eyalira Jacob Okal; Yanfei Wu; Shahid Iqbal; Zhaorui Liu; Yuwei Hu; Na Hu; Tingfang Zhong; Jingxian Li; Dongmei Yu; Bishal Gurung; Dong Liu; Peter Mortimer; et al. (Bioresource Technology, 2025)

A new norlignan and other compounds from Artemisia frigida Willd - Xin-Ya Dong; Ru-Ya Li; Hong-Xia Tang; Ya-Jie Li; Jun Chen; Jin-Guo Luo; Na Yu; Xiang-Wei Xu; Xu-Dong Zhou (Biochemical Systematics and Ecology, 2025)

Comparative Evaluation of Spores and Vegetative Forms of Bacillus subtilis and Bacillus licheniformis on Probiotic Functionality In Vitro and In Vivo - Hua Xie; Tianfei Yu; Qiwen Zhou; Kai Na; Shuang Lu; Li Zhang; Xiaohua Guo (Probiotics and Antimicrobial Proteins, 2025)

Epithelial sodium channel in dendritic cells participates in high-fat-induced inflammatory responses - Xu Li; Shi-Li Zhou; Lin Bai; Chun-Lei Yu; Na Niu (Molecular Biology Reports, 2025)

Effects of vertical dispersal on subsurface soil microbial communities - Youqian Li; Yifan Wang; Haifeng Lu; Meng Na; Jihai Zhou; Shangqi Xu (Applied Soil Ecology, 2025)

Comparison of Muscle Texture Characteristics and Nutritional Composition Between Gene-Edited Intermuscular-Bone-Free Crucian Carp and Other Varieties - Huijie Zhou; Zhipeng Sun; Tan Zhang; Tingting Zhang; Ting Yan; Huan Xu; Mingliang Wei; Yashan Yin; Na Li; Youyi Kuang; Guangxiang Tong (Fishes, 2025)
The intermuscular-bone-free crucian carp (Carassius auratus, WUCI), developed through CRISPR/Cas9-mediated bmp6a and bmp6b knockout, offers advantages in consumer acceptance and processing efficiency. However, its effects on muscle texture and nutritional quality have not been fully elucidated. In this study, we compared the F3 generation of WUCI with its sibling wild-type crucian carp (Carassius auratus, WT), Songpu silver crucian carp (Carassius gibelio var. Songpu, SPYJ), and Fangzheng silver crucian carp (Carassius gibelio var. Fangzheng, FZYJ), focusing on muscle texture characteristics and nutritional attributes. WUCI exhibited significantly higher shear force but lower hardness than most comparison groups, with no substantial differences in muscle fiber morphology. Amino acid profiles were similar among all groups. WUCI showed lower crude fat content than WT but higher than FZYJ, and comparable levels of polyunsaturated fatty acids (PUFA), n-3 fatty acids, docosahexaenoic acid (DHA), and eicosapentaenoic acid (EPA) to WT and SPYJ. These findings indicate that the knockout of bmp6a and bmp6b does not alter muscle mass in crucian carp, supporting the potential of WUCI for commercial adoption as a gene-edited consumer-oriented fish product.

Elucidating the material basis and therapeutic mechanisms of Shaoma Zhijing granules for tourette syndrome by UPLC/Q-TOF-MS and multiple models - Qian Zhao; Xin-Xin Xu; Jin-Na Yang; Li-Juan Pei; Zhou-Yi Xie; Wen-Jia Wang; Jing-Xuan Fu; Zhao-Hui Song; He Sun; Kai-Jing Yan; Hui Wang; Yun-Hui Hu (Metabolic Brain Disease, 2025)

Performance activation and syngas evolution mechanism of Ca-based industrial waste carbide slag on catalytic gasification of Mongolian bituminous coal - Zhiqing Lian; Guoyu Mao; Yanpeng Ban; Keduan Zhi; Jianxiu Hao; Huacong Zhou; Na Li; Quansheng Liu (Fuel, 2025)

Biomimetic GNPs-interwoven photonic molecularly imprinted polymer for the colored determination of trace 17β-estradiol - Jiayue Zhou; Dongmei Li; Tiantian Li; Ziwei Chen; Zhuxin Chang; Guanggui Yu; Ruicong Zhou; Linyuan Wang; Yinuo Chen; Jie Zhao; Huan Liu; Na Sai (Food Chemistry, 2025)

The embeddedness of bioactive molecules: structural characterization and functional analysis of almond protein-phloretin-L arabinose ternary complexes - Yongsong Zhang; Qian Zhou; Zun Li; Bin Wu; Chao Li; Na Xia (Food Chemistry, 2025)

Nanostructure-enhanced Raman spectroscopy for sensitive and on-site monitoring of anabolic-androgenic steroids in food and drug products - Na Zhou; Yu Zeng; Ting Li; Qiuwen Huang; Yushi Chen; Siqing Liu; Xiaojun Luo; Xiaojun Deng (Food Chemistry, 2025)

Cyano cyclization-anchoring strategy breaks the activity-stability trade-off in COF photocatalysts - Xia-Jun Jin; Jing-Qi Liu; Hong-Xia Zhang; Qiang-Qiang Yu; Hong-Zhi Zhou; De-Ming Kong; Li-Na Zhu (Chemical Engineering Journal, 2025)

Ethylene-responsive factor HvERF72 regulates starch synthesis and B-type starch granules initiation in barley - Gaozong Zhou; Jinjin Ding; Yulong Li; Qiang Xu; Yazhou Zhang; Huaping Tang; Pengfei Qi; Mei Deng; Jian Ma; Guoyue Chen; Jirui Wang; Na Lin; et al. (Carbohydrate Polymers, 2025)

Involvement of ductal reaction in Di-(2-ethylhexyl)-phthalate-caused hepatic fibrosis: Molecular mechanisms and potential intervention strategies - Xinru Du; Shu Zhang; Sha Liu; Yancheng Gao; Zhendong Wang; Na Dong; Sisi Song; Qinming Hui; Ziyi Wang; Yue Ma; Chunxiao Zhou; Ye Yang; et al. (Chemico-Biological Interactions, 2025)

Interdecadal shift in North Indian Ocean-South China Sea influence on the evolution of the East Asian summer monsoon from July to August - Jiazhe Duan; Hua Li; Na Yang; Yong Liu; Huixin Li; Yang Jiao; Botao Zhou (Atmospheric Research, 2025)

Investigation of the South Atlantic Anomaly (SAA) by proton flux variabilities based on 6 years’ CSES data - Lu Wang; Zhenxia Zhang; Xinqiao Li; Zhenghua An; Yanbing Xu; Ping Wang; Hong Lu; Xiaoyun Zhao; Dali Zhang; Xiaohua Liang; Zhiqiang Ding; Shujie Li; et al. (Science China Earth Sciences, 2025)

Effects of selenium–cadmium interactions on soil cadmium forms and the enrichment of selenium and cadmium in rice - Tianyi Lu; Yong He; Yanmei Ai; Meng Na; Shangqi Xu; Kun Cheng; Daming Li; Jihai Zhou (Plant and Soil, 2025)

Jaagichlorella menglunensis sp. nov. (Watanabeales, Chlorophyta), a new coccoid green alga isolated from China - Huiyin Song; Rongli Guan; Tian He; Langyue Zhang; Tiantian Li; Junfei Zhou; Yuxin Hu; Shuyin Li; Feng Liu; Lun Li; Na Zhang; Huafeng Xiao; et al. (Journal of Oceanology and Limnology, 2025)

Effects of temperature and moisture on the co-inoculation remediation of petroleum-polluted soil by bacteria and nematodes - Youqian Li; Meng Na; Jiajie Tang; Shangqi Xu; Jihai Zhou (Applied Soil Ecology, 2025)

miR-133b regulation of wbp2 in ovaries is conserved among teleosts - Jiayu Zhou; Qianwen Min; Xubing Ba; Zhaoqiu Qu; Zhenjun Zhuang; Biao Yuan; Xin Yi; Ruojing Li; Na Zhao; Bo Zhang (Acta Oceanologica Sinica, 2025)

Abscisic acid application enhances cadmium accumulation in Sedum plumbizincicola by controlling photosynthesis, hormone signaling and antioxidant defense - Meng Na; Daokun Liu; Shangqi Xu; Xiaoping Li; Xianqing Zheng; Jihai Zhou (Plant Science, 2025)

PEDUNCLE LENGTH 1 regulates wheat peduncle elongation through brassinosteroid signaling pathway - Hong Liu; Liya Zhi; Hualiang Qiao; Yanxiao Niu; Jianxiu Shang; Hao Zhang; Wenzhao Xie; Yazhou Xuan; Wenqing Li; Jijie Li; Xinyu Zhang; Liuge Xue; et al. (Molecular Plant, 2025)

Heteroaggregation between polystyrene micro(nano)plastics and dibutyl phthalate mediates toxicity reduction in macroalgae: Physiological and transcriptomic evidence from Gracilariopsis lemaneiformis - Yuanxia Li; Xiaoqian Zhang; Nianjun Xu; Mingze Chen; Wenting Tang; Na Zhou; Ting Zeng; Xue Sun; Zeming Zhang (Journal of Hazardous Materials, 2025)

Intrinsic electron transfer kinetics of electroactive granular sludge bioanode boosting bio-electro-Fenton efficiency - Bao-Gang Fu; Shu-Na Li; Xiangtong Zhou; Xiang Xiao; Liang Cheng; Yang-Yang Yu (Journal of Environmental Chemical Engineering, 2025)

Acid-resistant ZrO2/PPy nanocomposite for efficient fluoride removal from hydrochloric acid - Yan Li; Xin Huang; Fengzheng Liu; Sanli Yin; Zijian Zhou; Bin Lu; Ting Wang; Na Wang; Hongxun Hao (Journal of Environmental Chemical Engineering, 2025)

Characterization and efficacy of α-glucosidase inhibitory peptides from enzymatically hydrolyzed Peanut meal - Sen Zhou; Zhiran Zhang; Shengxin Li; Mengkai Liu; Ziyan Zhang; Na Wang; Jie Sun (Food Research International, 2025)

Correction to: Exploring the bioactive ingredients of three traditional Chinese medicine formulas against age-related hearing loss through network pharmacology and experimental validation - Wenying Shi; Qi Zhao; Hongwei Gao; Yaxin Yang; Zhiyong Tan; Na Li; Hongjie Wang; Yonghua Ji; You Zhou (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Genetic burden and multidimensional predictors in prenatal diagnosis of fetal congenital diaphragmatic hernia - Ruibin Huang; Fang Fu; Shanshan Mei; Liyuan Liu; Wei Zhong; Jin Han; Qiuxia Yu; Hang Zhou; Chunling Ma; Li Zhen; Min Pan; Qiong Deng; et al. (Human Genetics, 2025)

Green manure roots return drives saline-alkali soil organic carbon accumulation via microbial necromass formation - Fangdi Chang; Hongyuan Zhang; Peiyi Zhao; Na Zhao; Jiashen Song; Ru Yu; Jing Wang; Xiquan Wang; Dongxun Han; Xiaodong Liu; Jie Zhou; Yuyi Li (Soil and Tillage Research, 2025)

Evaluation of ecological risks of antibiotics in Danjiangkou Reservoir basing on toxicity potency and antibiotic resistance genes transfer - Ruiwen Li; Yindan Zhang; Shuyin Li; Shan Chen; Chengchen Huang; Lihua Yang; Na Zheng; Yongyong Guo; Jian Han; Bingsheng Zhou; Yingcai Wang (Science of The Total Environment, 2025)

Unveiling the multifunctional roles of karrikin as a novel phytohormone in cadmium detoxification of bread wheat (Triticum aestivum L.) - Ting Zhou; Yu-shan Xiao; Yong-le Fu; Hao Li; Rui Cui; Ying-na Feng; Zheng-fu Zhou; Ying-peng Hua (Journal of Hazardous Materials, 2025)

Polystyrene microplastic pollution induces species-specific shifts in root traits and rhizosphere conditions in a temperate forest - Yingtong Zhou; Wei Guo; Ivano Brunner; Jiaxin Liu; Xiaoyue Na; Qinrong Tang; Junni Wang; Cunguo Wang; Mai-He Li (Journal of Hazardous Materials, 2025)

A Co(III)-dipyrazolate framework for atmospheric CO2 photoreduction - Yingjie Wang; Xiang-Jing Kong; Guang-Rui Si; Tao He; Da-Yu Chen; Jian-Yu Zhang; Na Xing; A-Wu Zhou; Jian-Rong Li (Chemical Engineering Journal, 2025)

Consecutive application of peanut shell and its biochar triggered different soil organic carbon mineralization by altering microbial resource availability and composition in sweet potato cropping systems - Meng Na; Jinping Feng; Shangqi Xu; Xiaoping Li; Xianqing Zheng; Jihai Zhou (Plant and Soil, 2025)

Multiple Impacts of Climate Change and Anthropogenic Activities on Lacustrine Trophic State - Ge Xie; Yibo Zhang; Qing Wang; Kun Shi; Yunlin Zhang; Yongqiang Zhou; Boqiang Qin; Junliang He; Na Li (Global Change Biology, 2025)
The trophic state index (TSI) serves as a fundamental indicator for evaluating the water quality of lake ecosystems. Under climate change and human activities, global lake TSI has changed significantly, yet its response mechanisms remain unclear. To address this challenge, we developed a generalized TSI estimation model by integrating semi‐analytical algorithms with machine learning techniques, based on a comprehensive dataset comprising 3756 pairs of in situ measurements and remote sensing observations. The developed model demonstrated superior predictive performance with R 2 of 0.77 and RMSE of 8.25 for the testing dataset. Applying the model, we reconstructed a 21‐year time series (2003–2023) TSI for 14,189 global lakes with surface area ≥ 10 km 2 . The global mean TSI was estimated to be 54.07 ± 0.31. Among the lakes, 4.1% were classified as oligotrophic (TSI ≤ 38), 18.9% as mesotrophic (38 61). Globally, TSI showed a significantly increasing trend at a rate of 0.19 per decade ( p

Screening and characterization of an Alcaligenes sp. HHVWA23 and the efficiency of nitrogen removal by biochar immobilization - Teng Li; Chang Liu; Zeyan Xi; Na Li; Liwen Liao; Yulong Zhou; Yaobing Li; Luqing Pan (Journal of Environmental Management, 2025)

High-conductivity and high-ion-mobility sodium lignosulfonate-based hydrogel electrolyte for dendrite-free zinc-ion batteries - Na Luo; Zishuo Li; Xudong Zhou; Sijia Jin; Yang Liu; Haibo Huang; Jidong Dong; Dawei Zhang; Pengfei Huo (Journal of Environmental Chemical Engineering, 2025)

In situ construction of an organic/metal bridging interface toward zinc metal anode with ultra-long cycle life of 5000 h - Zhe Gong; Han Yu; Zhuo Li; Chenyi Yang; Feifei Gao; Pengfei Wang; Na Sun; Mingdong Zhou; Kai Zhu; Yaguang Sun (Chemical Engineering Journal, 2025)

The growth and nutrient removal properties of a newly isolated Desmodesmus sp. XNY-2104 under mixotrophic and heterotrophic conditions using volatile fatty acids (VFAs) - Jie Li; Na Liu; Wenbao Yan; Qi Zhao; Xinglong Zhou; Cong Jia; Chongqing Xu; Xiaozhe Song; Mingming Song (Biomass and Bioenergy, 2025)

Chemotaxonomic significance of coumarins and alkaloids in the leaves of Glehnia littoralis - Sainan Li; Shuo Tian; Jisu Park; Wei Zhou; Renbo An; MinKyun Na (Biochemical Systematics and Ecology, 2025)

Contrasting fungal community assembly mechanisms in bulk soil and rhizosphere of Torreya grandis across a 900-year age gradient - Bin Wang; Xiaofan Na; Shengyi Huang; Zhengcai Li; Zhichun Zhou; Juying Huang; Meiyun Pu; Zhenyu Cheng; Xiaoqi He (Plant and Soil, 2025)

Fermented Chinese herbal medicines combined with probiotics promote growth of fattening lambs under heat stress by modulating rumen mucosal barrier functions - Shoupei Zhao; Xinsheng Sun; Na Zhao; Hongwei Zhang; Gaofu Wang; Lu Zhang; Yuqing Liu; Haitong Yang; Jianjie Li; Jia Zhou; Yuhong Gao (Animal Feed Science and Technology, 2025)

Cytokine profiling in COVID-19 patients by using ion mobility-mass spectrometry-based parallel reaction monitoring - Ling Yan; Chenrui Yuan; Runhou Zhou; Li Zhong; Kelvin Kai-Wang To; Na Liu; Xin Diao; Guangshan Xie; Hongzhi Zhao; Haijiang Wu; Lin Zhu; Zhiwei Chen; et al. (Analytica Chimica Acta, 2025)

Comparative analysis of the seasonal and intra-seasonal geocenter motion derived from GNSS displacements: IGS Repro3 and Repro2 - Yuxin Zhou; Na Wei; Yanlin Li (Advances in Space Research, 2025)

Multi-Parameter Analysis of Stress Accumulation and Evolution Prior to the 2020 Guye MS5.1 Earthquake, North China: Insights from Apparent Stress, b-value, and Focal Mechanism Consistency - Xu-dong Ma; Lei Guo; Li-na Sun; Yi Zhou; Zhi-hua Ding (Applied Geophysics, 2025)

Taurine related pathways effect the potential domestication of wild Larimichthys crocea adapt to stress environment - Xubing Ba; Zhenjun Zhuang; Zebin Zhou; Jiayu Zhou; Qianwen Min; Biao Yuan; Xin Yi; Ruojing Li; Zhaoqiu Qu; Na Zhao; Bo Zhang (Aquaculture, 2025)

Tissue and cell types infected by Ecytonucleospora hepatopenaei (EHP) - Yuan Wang; Shi-ting Lin; Ming Zhao; Peng Di; Jun-fang Zhou; Shou-hu Li; Yan-qing Huang; Ying Na; Xin-cang Li; Wen-hong Fang (Journal of Invertebrate Pathology, 2025)

Mechanisms and pollution characteristics of heavy metal flow in China's non-ferrous metal industry - Na Li; Zhenjiang Guo; Chengkang Gao; Huan You; Huijing Zhou; Xinhong Zhang; Tao Zheng (Journal of Cleaner Production, 2025)

Effects of dietary protein-oxidized soybean meal and quercetin on gel properties, microstructure, molecular structure and proteomics of egg white in laying hens - Hengzhi Li; Na Chen; Yun Shao; Chunxiao Wang; Yanmin Zhou; Shugang Li; Shuangjie Zhu (Food Chemistry, 2025)

Mitigating the impacts of ionospheric irregularities on GPS precise positioning by refined cycle slip threshold - Wei Li; Shuli Song; Tianyang Bai; Na Cheng; Weili Zhou; Chao Yu (GPS Solutions, 2025)

Selection and identification of the ssDNA aptamer against polymyxin B sulfate - Zhuxin Chang; Jiayue Zhou; Dongmei Li; Haoran Wang; Mengmeng Chen; Linyuan Liu; Jia Ding; Yu Wang; Zhixian Gao; Na Sai (Analytica Chimica Acta, 2025)

Genetic deletion of microRNA-15a/16-1 in pericytes stimulates cerebral angiogenesis and promotes functional recovery after ischemic stroke - Ping Sun; Yang Xu; Tianqing Xiong; Shun Li; Na Qiu; Chao Zhou; Jiefei Wang; Alexander Chang; Uma R. Chandran; Ke-Jie Yin (Angiogenesis, 2025)

A cobalt ferricyanide/ZIF-67/composted humus gel composite for improved cesium ion removal from wastewater - Hao Fang; Lu Yang; Jie Ni; Shanshan Feng; Wenhao Jia; Na Li; Xiaoyi Ma; Zhengwei Zhou; Yao Zhang; Sheng Feng (Journal of Water Process Engineering, 2025)

Synergetic effects of p-toluenesulfonic acid and acetic acid on the catalytic depolymerization of bisphenol A polycarbonate waste into valuable chemicals - Yafang Zhang; Heya Na; Jianxiu Hao; Yanpeng Ban; Na Li; Keduan Zhi; Shukun Le; Huacong Zhou; Quansheng Liu (Journal of Environmental Chemical Engineering, 2025)

Safety evaluation, removal characteristics, mechanism exploration, and application potential of Lactococcus lactis GFWM17, a broad-spectrum bacteriostatic strain that simultaneously removes nitrogen and sulfide - Zeyan Xi; Teng Li; Liwen Liao; Na Li; Yulong Zhou; Luqing Pan (Journal of Environmental Chemical Engineering, 2025)

Overlooked formation of chlorinated coupling byproducts during phenol degradation with ferrate(VI) oxidation technology - Dan Tao; Yuxin Zhou; Laura Carter; Chengxuan Tian; Na Qin; Kehao Li; Fan Zhang (Journal of Environmental Sciences, 2025)

Unveiling fungal degradation pathways for polyurethane and polyethylene through enrichment cultures and metabolic analysis - Eyalira Jacob Okal; Jie Zhou; Yanfei Wu; Tingfang Zhong; Yue Tang; Zhengyu Sun; Ruifang Xu; Yuwei Hu; Na Hu; Jingxian Li; Samantha C. Karunarathna; Peter E. Mortimer; et al. (International Biodeterioration & Biodegradation, 2025)

Characterization and gelling properties of pectin extracted from Gardenia fruit - Xuan Wang; Tian Tian; Na Li; Lingling Zheng; Yuyao Wu; Wei Bian; Jian-Lin Wu; Tingting Zhou (Food Hydrocolloids, 2025)

Chemical constituents of Ainsliaea fragrans and their chemotaxonomic significance - Xiao-Ting He; Yun-Na Wang; Xue-Mei Zhou; Jing-Jing Zhang; Xiao-Li Li; Wei-Lie Xiao (Biochemical Systematics and Ecology, 2025)

Deformation and protection of tunnels influenced by excavation dewatering in soft soil strata with leaky aquifers - Qinghan Li; Gang Zheng; Xuesong Cheng; Xiaorui Shi; Na Zhang; Shilong Zhou; Wenlong Cheng (Tunnelling and Underground Space Technology, 2025)

Copper oxide nanoparticles disrupt lysosomal function and promote foam cell formation in RAW264.7 macrophages - Yilin Luo; Kun Zhang; Lejiao Mao; Meiling Tan; Xiaomei Dong; Na Li; Yuexing Zhou; Chengzhi Chen; Zhen Zou; Jun Zhang (Toxicology, 2025)

Associations of multiple metals exposure with immunoglobulin levels in pregnant women: Hangzhou Birth Cohort Study - Jiena Zhou; Lanfei Jin; Yexinyi Zhou; Kunhong Zhong; Kegui Huang; Qi Zhang; Jun Tang; Xue Zhang; Lihe Peng; Shuai Li; Na Lv; Dongdong Yu; et al. (Journal of Environmental Sciences, 2025)

Overexpression of the Wbl family regulator whiDsbh modulates secondary metabolite biosynthesis in Streptomyces - Xuedong Zhang; Jiabin Wang; Haoran Shi; Na Zhou; Shanshan Li; Lan Ye; Wensheng Xiang; Xiangjing Wang; Yanyan Zhang (World Journal of Microbiology and Biotechnology, 2025)

Inhibition of Vascular Endothelial Growth Factor Reduces Photoreceptor Death in Retinal Neovascular Disease via Neurotrophic Modulation in Müller Glia - Shuang Gao; Sha Gao; Yanuo Wang; Lu Xiang; Hanwei Peng; Gong Chen; Jianmin Xu; Qiong Zhang; Caihong Zhu; Yingming Zhou; Na Li; Xi Shen (Molecular Neurobiology, 2025)

Facile preparation of N/P co-doped mesoporous biochar for efficient removal of methylene blue from aqueous solutions: A 2D-FTIR-COS, adsorption mechanism analysis, and fixed-bed column study - Shisuo Fan; Manquan Zhao; Jiajia Luo; Weicheng Li; Xinru Fan; Na Zhou; Huacheng Xu; Yuanzhi Shi (Journal of Water Process Engineering, 2025)

In-situ constructed ZnAl2O4/A-MoS2 Z-scheme heterojunction for visible-light-thermo cascade catalytic CO2 cycloaddition - Congcong Zhang; Bin Jiang; Runjia Mou; Haochen Shen; Qi Zhou; Longfei Zhang; Jingshuai Li; Na Yang; Luhong Zhang (Journal of Environmental Chemical Engineering, 2025)

Low loading palladium-carbon catalyst for efficient rosin disproportionation: Structure–activity relationship, reaction pathway, and catalytic dehydrogenation mechanism - Yifan Niu; Siyu Gong; Na Li; Xian Zhou; Shaohua Ju; Yongwan Gu (Fuel, 2025)

Insight into the structural properties and CO2 gasification reactivity of biomass and lignite co-pyrolysis char - Chunfu Yun; Maoguang An; Yanpeng Ban; Huacong Zhou; Jianxiu Hao; Na Li; Keduan Zhi; Yunfei Wang; Quansheng Liu (Fuel, 2025)

Review on recent advancements in understanding acetylsalicylic acid-induced gastrointestinal injury: mechanisms, medication, and dosage refinement - Jiahui Zhou; Na Li; Xinzhong Li; Jingxue Ye; Min Wang; Guibo Sun (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Exploring the bioactive ingredients of three traditional Chinese medicine formulas against age-related hearing loss through network pharmacology and experimental validation - Wenying Shi; Qi Zhao; Hongwei Gao; Yaxin Yang; Zhiyong Tan; Na Li; Hongjie Wang; Yonghua Ji; You Zhou (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Involvement of BK Channels and Ryanodine Receptors in Salicylate-induced Tinnitus - Wenying Shi; Qi Zhao; Hongwei Gao; Chao Yang; Zhiyong Tan; Na Li; Feng Jiang; Hongjie Wang; Yonghua Ji; You Zhou (Molecular Neurobiology, 2025)

Changes in microbial carbon cycling functions along rice cultivation chronosequences in saline-alkali soils - Shangqi Xu; Meng Na; Yongjie Huang; Jie Zhang; Jihai Zhou; Lu-Jun Li (Soil Biology and Biochemistry, 2025)

Melatonin application enhances the remediation of cadmium-contaminated soils by Cinnamomum camphora - Meng Na; Chenyang Zhang; Shangqi Xu; Xiaoping Li; Shoubiao Zhou; Jihai Zhou (Science of The Total Environment, 2025)

Unveiling the microbial mysteries of mulberry rhizosphere in saline-alkaline soils - Na Li; Jisheng Li; Shengjie Zhang; Xiaojun Lan; Heng Zhou (Rhizosphere, 2025)

γ-Radiation synthesis of bis-amidoxime-based three-dimensional hydrogel uranium adsorbent based on nano-rubber toughening - Bo Tian; Wenze Li; Jianwei Zhang; Jinfeng Li; Na Zhou; Wa Gao; Nan Zhang; Hongtao Zhao (Journal of Water Process Engineering, 2025)

Chameleon-inspired molecular imprinted polymer with bicolored states for visual and stable detection of diethylstilbestrol in water and food samples - Dongmei Li; Jiayue Zhou; Zhuxin Chang; Hongwei Zhao; Nan Zhang; Huan Xia; Linyuan Wang; Jie Zhao; Guanggui Yu; Zhongze Fang; Na Sai (Food Chemistry, 2025)

Is the pollutant removed by the rejection of nanofiltration (NF) membranes in a NF-based membrane bioreactor (MBRNF)? - Chu Zhou; Xuan Zhou; Fujie Kuang; Na Li; Senlin Shao (Desalination, 2025)

A cationic hydrogel for visual diagnosis and treatment of bacterial-infected wounds via mild, on-demand dual-phototherapy - Yi Cao; Na Li; Manyu Chen; Hongfu Cao; Chen Zhou; Zuqin Dong; Jie Liang; Qiguang Wang; Yujiang Fan; Xingdong Zhang (Chemical Engineering Journal, 2025)

Microcarrier stiffness controls human amniotic epithelial cells (hAECs) proliferation and epithelial-mesenchymal transition (EMT) via remodeling ECM and Wnt/β-catenin pathway - Jia Tian; Wangping Hao; Juan Li; Xiangming Na; Shuang Wang; Wei Wei; Yuefeng Lu; Yangyang Cui; Wencheng Zhang; Zhiying He; Guanghui Ma; Weiqing Zhou (Chemical Engineering Journal, 2025)

Regional high iron deposition on brain quantitative susceptibility mapping correlates with cognitive decline in chronic kidney disease patients - Yuan Li; Yuhan Jiang; Bingbing Gao; Na Liu; Yukun Zhang; Huiling Zhou; Qingwei Song; Nan Wang; Yanwei Miao (Brain Imaging and Behavior, 2025)

Integrated omics analysis reveals the effect of feeding scarcity on the lipid metabolism and apoptosis in Nibea coibor - Zhaoqiu Qu; Biao Yuan; Ruojing Li; Xubing Ba; Zhenjun Zhuang; Xin Yi; Jiayu Zhou; Qianwen Min; Zhongdian Dong; Na Zhao; Bo Zhang (Aquaculture, 2025)

Fe2+ inhibits spring viraemia of carp virus proliferation via ATG14-dependent autophagy - Zhuo-Cong Li; Can Zhang; Na Xu; Xiao Xu; Ke-Jia Han; Chu-Jing Zhou; Yang-Yang Wang; Bao-Jie Cui; Dan-Dan Chen; Long-Feng Lu; Shun Li (Aquaculture, 2025)

KCNJ15 inhibits chemical-induced lung carcinogenesis and progression through GNB1 mediated Hippo pathway - Hong-qiang Chen; Na Wang; Yong Zeng; Yu Shi; Zhe Zhang; Jiang-ying Li; Ya-wen Li; Shuang-wu Deng; Zi-yuan Zhou; Wen-bin Liu (Toxicology, 2025)

Association between maternal serum zinc and birth weight is modified by neonatal SOD2 polymorphism and promoter methylation - Yuting Zeng; Yalong Wang; Yanan He; Qinyang Li; Ruiqin Chen; Cuiping Wu; Na Li; Xinya Cheng; Yuhui Du; Fangfang Yu; Yue Ba; Guoyu Zhou (Journal of Trace Elements in Medicine and Biology, 2025)

Remediation of various phenanthrene-contaminated soils using persulfate-Pseudomonas aeruginosa GZ7: Soil properties, radical formation, and microbial community - Na Liu; Xiangyuan Zhou; Lin Wu; Tao Jin; Kang Li; Liping Wang (Journal of Environmental Chemical Engineering, 2025)

Carbon dots based cascading nanozymes mitigate phytotoxicity in lettuces under imidacloprid stress - Fengqiong Chen; Ziyan Zhou; Na Yang; Qin Jiang; Xuejie Zhang; Haoran Zhang; Yinjian Zheng; Wei Li; Bingfu Lei (Food Chemistry, 2025)

Using multi-modal spectroscopy technology and microscopic analysis to explore the regulation of ultra-high pressure heat-assisted treatment on the texture of ready-to-eat shrimp during storage - Na Li; Zhifeng Tan; Ruida Ma; Yafang Song; Rong Liu; Jiaxin Zhao; Ningbo Qin; Yahong Li; Xiaoyang Liu; Dayong Zhou; Deyang Li (Food Chemistry, 2025)

Allicin amplifies disulfidptosis during GOx catalyzing glucose-starvation for cancer therapy via simultaneous antimicrobial and antitumor intervention - Taotao Huo; Bin Zhu; Xiaoyu Shan; Jiaqi Song; Ziyi Wang; Jianxu Zhou; Xianpeng Zhang; Yuquan Bai; Chengcheng Liu; Yiyang Zhao; Na Mei; Yazhong Bu; et al. (Chemical Engineering Journal, 2025)

Engineering a circular DNA agonist to activate MET signaling for promoting angiogenesis and regeneration of diabetic ulcer - Jun Zhu; Meixia Wang; Zhu Li; Ceheng Liao; Yangbing Li; Zhixi Duan; Xinxin Zhang; Yizhi Zhang; Fang He; Zhou Nie; Hong-Hui Wang; Na Cai; et al. (Chemical Engineering Journal, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

The deformation characteristics of modified lightweight expanded polystyrene soils under cyclical loading - Ping Jiang; Yuming Fu; Wei Wang; Xuhui Zhou; Na Li; Huaqiang Tao (Soil Dynamics and Earthquake Engineering, 2025)

Effects of wetland disturbance on methane emissions and influential factors: A global meta-analysis of field studies - Shangqi Xu; Xia Liu; Meng Na; Xinyi Yu; Youqian Li; Yongjie Huang; Jie Zhang; Jihai Zhou; Chunjie Tian (Science of The Total Environment, 2025)

Benzofurans and dibenzofurans from galls on twigs of the endangered Chinese endemic tree Parrotia subaequalis and their inhibitory properties against Staphylococcus aureus and ATP-citrate lyase - Peng-Jun Zhou; Xi-Ying Wu; Ze-Yu Zhao; Yi Zang; Zhong-Shuai Sun; Yue-Ling Li; Na Li; Juan Xiong; Yeun-Mun Choo; Ze-Xin Jin; Jia Li; Jin-Feng Hu (Phytochemistry, 2025)

ALFIN-like proteins link histone H3K4me3 to H2A ubiquitination and coordinate diverse chromatin modifications in Arabidopsis - Xiao-Min Su; Dan-Yang Yuan; Na Liu; Zhao-Chen Zhang; Minqi Yang; Lin Li; She Chen; Yue Zhou; Xin-Jian He (Molecular Plant, 2025)

Unveiling the spatiotemporal heterogeneity and driving mechanisms of carbon storage changes in response to land use/land cover changes under different future scenarios: Insights from the GMOP-SEM model - Tianlu Jin; Peixing Zhang; Na Zhou; Si Li (Journal of Cleaner Production, 2025)

Microbiome changes and characteristics under nutrient injection for enhanced oil production at Daqing oilfield - Zi-Yue Fu; Wen-Tao Chen; Gui-Na Qi; Zhao-wei Hou; Yi-Fan Liu; Li-Bin Shou; Lei Zhou; Shi-Zhong Yang; Xiao-Lin Wu; Ji-Dong Gu; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2025)

Self-supporting coal liquefaction residue electrode intensifies efficient coupling of hydrogen evolution and carbon dots preparation - Ruzhan Bai; Xing Zhou; Quansheng Liu; Tong Zhang; Jianming Fan; Huacong Zhou; Yanpeng Ban; Na Li; Xuzhong Gong (Chemical Engineering Journal, 2025)

The impeded film-formation kinetics with ameliorated carrier trap density to construct efficient as-cast organic solar cells through short multi-branched alkylthio chains strategy - Ling Li; Na Li; Jiefeng Hai; Shenzheng Gao; Hao Xu; Ming Luo; Xinjie Zhou; Xiaoyu Shi; Shanlei Xu; Xueming Li; Zhenhuan Lu; Youyong Pang; et al. (Chemical Engineering Journal, 2025)

Comparison of molecular testing methods for diagnosing non-tuberculous mycobacterial infections - Leilei Wang; Yu Chen; Qingqing Wang; Jue Pan; Rong Bao; Wenting Jin; Yumeng Yao; Tingting Fang; Na Li; Sichun Luan; Xiaoyu Yin; Le Qin; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

The coupling effect and ecological risk assessment of iron, manganese, and arsenic in the water environment of the central Yangtze River Basin, China - Meiyan Hu; Peijiang Zhou; Chao Meng; Xiaobin Li; Jingyi Xie; Xuan Zhang; Guangshui Na (Environmental Geochemistry and Health, 2025)

Quantitative study on the relationship between land use and land cover and diatom community in urban streams - Xiang Chen; Weiqi Zhou; Wenjuan Yu; Mingwei Yang; Dong Sheng; Kangyong Li; Na Li; Yuling Ou; Feng Wei (Environmental Science and Pollution Research, 2024)

Meta-analysis: Global patterns and drivers of denitrification, anammox and DNRA rates in wetland and marine ecosystems - Jiaqi Lun; Wenxi Zhou; Mengyue Sun; Na Li; Wenchong Shi; Zheng Gao; Mingcong Li (Science of The Total Environment, 2024)

Intimate microbe-water-mineral interactions mediate alkalization in the pyroxene-rich iron ore mines in Panxi area, Southwest China - Yu He; Yongzhe Li; Yue Pan; Jianying Shang; Weimin Sun; Meng Wang; Hao Fan; Robert A. Sanford; Na Wei; Shuming Peng; Daihong Xie; Weiguang Zhang; et al. (Journal of Hazardous Materials, 2024)

Contribution for lake phytoplankton community succession under multi-source artificial hydrological regulation - Bowen Sun; Na Li; Guoyu Wang; Xueping Gao; Xushen Zhou; Fanqing Kong (Journal of Environmental Management, 2024)

Effect of probiotic fermentation on the extraction rate and bioactivity of plant-based polysaccharides: A review - Zichao Wang; Yi Zheng; Yibo Dai; Rongchao Yang; Renyong Zhao; Gangchun Sun; Wen-Wen Zhou; Shouai Feng; Yingjie Feng; Na Li; Jinchu Yang; Huiru Zhang; et al. (Innovative Food Science & Emerging Technologies, 2024)

Fully biobased unsymmetric bisphenols from condensation of lignin-derived monophenols for non-isocyanate polyurethane synthesis - Na Shi; Yongwei Ni; Zhenjiang Li; Kai Chen; Daiqing Zhou; Min Zhang; Weizhou Huang; Yujia Wang; Ming Chen; Kai Guo (Fuel, 2024)

Novel insight into calcium-catalyzed steam gasification behaviors of lignite - Bin Zhao; Lufeng Liu; Quansheng Liu; Na Li; Huacong Zhou; Yanpeng Ban (Fuel, 2024)

Effect of ultra-high pressure heat-assisted technology combined with L-cysteine on the color of ready-to-eat shrimp during storage - Na Li; Yefan Wang; Zhifeng Tan; Yunpeng Xu; Xiaoyang Liu; Yuxin Liu; Dayong Zhou; Deyang Li (Food Chemistry, 2024)

Morphology and elemental composition of individual solid dust particles: From different sources to the atmosphere - Wenhua Wang; Mengyang Wang; Longyi Shao; Xiuyan Zhou; Zhe Zhao; Na Li; Hui Zhou; Weijun Li (Atmospheric Environment, 2024)

Drinking water safety improvement and future challenge of lakes and reservoirs - Yunlin Zhang; Jianming Deng; Yongqiang Zhou; Yibo Zhang; Boqiang Qin; Chunqiao Song; Kun Shi; Guangwei Zhu; Xuejiao Hou; Yinjun Zhang; Shiwen He; R. Iestyn Woolway; et al. (Science Bulletin, 2024)

Acne-related UVA-induced facial fluorescence: An exploratory study from physiological properties to tissue structure information - Xing Ren; Yanan Sun; Yuxin Zhang; Na Zhou; Yunong Wang; Lishuang Li; Xinyu Gao; Yuman Ma; Xianyu Li; Zhe Shu; Honghui He; Yi Wang (Journal of Photochemistry and Photobiology B: Biology, 2024)

Investigation of isomerization and oxidation of astaxanthin in ready-to-eat Litopenaeus vannamei during accelerated storage - Na Li; Xin Fan; Yefan Wang; Kexin Zhang; Rong Liu; Yunpeng Xu; Zhifeng Tan; Wensi Xu; Dayong Zhou; Deyang Li (Food Research International, 2024)

Dual-mode SERS/colorimetric sensing of nitrite in meat products based on multifunctional au NPs@COF composite - Rui Tan; Mei Zeng; Qiuwen Huang; Na Zhou; Mengjiang Deng; Yuanyuan Li; Xiaojun Luo (Food Chemistry, 2024)

RNA reading protein YTHDF2 mediates Benzo(k)fluoranthene induced male reproductive injury by regulating the stability of BCL2 - Ya-wen Li; Dan-dan Wang; Hong-qiang Chen; Yong Zeng; Na Wang; Yu Shi; Jiang-ying Li; Ni-ya Zhou; Da-peng Wang; Qing Chen; Xue Han; Jia Cao; et al. (Environmental Pollution, 2024)

Phthalates on indoor surfaces and associated exposure via surface touch behavior: Observation in university dormitories and its implications - Fangzhou Yuan; Yu Sun; Na Li; Jianping Cao; Nan Zhang; Daniel Mmereki; Zhonghua Wei; Rui Chen; Jinyu Zhou; Yousheng Xu; Zhongming Bu (Building and Environment, 2024)

Abundance, characteristics and ecological risk assessment of microplastics in ship ballast water in ports around Liaodong Peninsula, China - Qing Su; Yuxia Li; Na Lu; Ling Qu; Xin Zhou; Yue Yu; Daping Lu; Junsong Han; Jianbo Han; Xiaotong Xu; Xiaomeng Wang (Marine Pollution Bulletin, 2024)

The role of BTG2/PI3K/AKT pathway-mediated microglial activation in T-2 toxin-induced neurotoxicity - Xiukuan Li; Jinyun Long; Chunyan Yao; Xiaoling Liu; Na Li; Yumeng Zhou; Dawei Li; Guiyuan Xiong; Kexue Wang; Yuhui Hao; Ka Chen; Ziyuan Zhou; et al. (Toxicology Letters, 2024)

Multiple strategy for antibacterial effect via copper porphyrin doping polyphenolic aldehydes based covalent organic framework - Zi-Wen Zhou; Chun-Xiu Liu; Chun-Xian Cai; Yun-Jie Wei; Kun Li; Xiao-Qi Yu; Yan-Hong Liu; Na Wang (Journal of Environmental Chemical Engineering, 2024)

HZrO2@PPy nanocomposite for effective fluoride removal from environmental water - Yan Li; Qin Wang; Fengzheng Liu; Zijian Zhou; Xin Huang; Na Wang; Ting Wang; Hongxun Hao (Journal of Environmental Chemical Engineering, 2024)

Selective catalytic reduction of NO by CO over spinel CuFe2O4 catalyst: The vital role of oxygen vacancies - Chenyang Wu; Na Li; Yuqing Pan; Xiaole Chen; Lehang Chen; Qulan Zhou; Zhong Huang (Journal of Environmental Chemical Engineering, 2024)

A dual-signaling surface-enhanced Raman spectroscopy ratiometric strategy for ultrasensitive Hg2+ detection based on Au@Ag/COF composites - Yuanyuan Li; Na Zhou; Jiayu Yan; Kaixin Cui; Qiqi Chu; Xi Chen; Xiaojun Luo; Xiaojun Deng (Food Chemistry, 2024)

Beetle-inspired AuNPs semi-embedded colloidal crystal chips for the highly sensitive and colored detection of chloramphenicol in foods - Jiayue Zhou; Dongmei Li; Jie Nan; Nan Zhang; Hongwei Zhao; Huan Xia; Zhuxin Chang; Na Sai (Food Chemistry, 2024)

FTO mediates bisphenol F-induced blood-testis barrier impairment through regulating ferroptosis via YTHDF1/TfRc and YTHDF2/SLC7A11 signal axis - Yu Shi; Li Yin; Jiang-ying Li; Shi-meng Zhou; Na Wang; Hong-qiang Chen; Yong Zeng; Ya-wen Li; Wen-bin Liu (Environmental Pollution, 2024)

Decoding the fish genome opens a new era in important trait research and molecular breeding in China - Qian Zhou; Jialin Wang; Jiongtang Li; Zhangfan Chen; Na Wang; Ming Li; Lei Wang; Yufeng Si; Sheng Lu; Zhongkai Cui; Xuhui Liu; Songlin Chen (Science China Life Sciences, 2024)

Label-free SELEX of aptamers for ultra-sensitive electrochemical aptasensor detection of amanitin in wild mushrooms - Renxiang Yang; Changsong Zhao; Sheng Ding; Jia Ruan; Dongqiu Li; Yijia Xiang; Jie Zhou; Huilan Su; Na Li (Analytica Chimica Acta, 2024)

The association between short-term ozone exposure and fasting blood glucose levels in non-diabetic adults was more obvious in rural residents: the evidence from a typical “urban–rural dual structure” province in southwestern China - Xue-Jiao Li; Ling Li; Li Zhao; Ding-Yan Hu; Na-Na Ma; Hua Xiao; Da-Wei Li; Jie Zhou; Yi-Ying Wang; Ji Zhang; Tao Liu; Yue-Xu Jiang; et al. (Air Quality, Atmosphere & Health, 2024)

Ti3C2 quantum dots-modified oxygen-vacancy-rich BiOBr hollow microspheres toward optimized photocatalytic performance - Tao Cheng; Zipeng Xing; Na Zhang; Peng Sun; Hui Peng; Zhenzi Li; Nan Wang; Wei Zhou (Chemosphere, 2024)

Benzo(a)pyrene promotes the malignant progression of malignant-transformed BEAS-2B cells by regulating YTH N6-methyladenosine RNA binding protein 1 to inhibit ferroptosis - Na Wang; Hong-qiang Chen; Yong Zeng; Yu Shi; Zhe Zhang; Jiang-ying Li; Shi-meng Zhou; Ya-wen Li; Shuang-wu Deng; Xue Han; Zi-yuan Zhou; Mao-lin Yao; et al. (Toxicology, 2024)

Paospora carinifang n. gen., n. sp. (Microsporidia: Spragueidae), a parasite of the ridgetail white prawn, Palaemon carinicauda - Yuan Wang; Ying Na; Yan-qing Huang; Jun-fang Zhou; Shou-hu Li; Quan-lin Liu; Le-tian Li; Yuan-ge Chen; Wei Tian; Hai Chi; Xin-cang Li; Wen-hong Fang (Journal of Invertebrate Pathology, 2024)

Triple modal aptasensor arrays driven by CHA-mediated DNAzyme for signal-amplified atrazine pesticide accumulation monitoring in agricultural crops - Jintong Liu; Na Li; Linyao Ye; Lin Zhou; Guanghao Chen; Jie Tang; Heng Zhang; Hong Yang (Journal of Hazardous Materials, 2024)

Review of reactor systems for hydrogen production via ammonia decomposition - Na Li; Cheng Zhang; Dong Li; Wenbin Jiang; Fojin Zhou (Chemical Engineering Journal, 2024)

Identification of Autophagy-Related Candidate Genes in the Early Diagnosis of Alzheimer’s Disease and Exploration of Potential Molecular Mechanisms - Jian Wang; Xinhua Huo; Huiqin Zhou; Huasheng Liu; Xiaofeng Li; Na Lu; Xuan Sun (Molecular Neurobiology, 2024)

Neutrophil-secreted S100A8/A9 participates in fatty liver injury and fibrosis by promoting myofibroblast migration - Na Chang; Yuran Liu; Weiyang Li; Yuehan Ma; Xuan Zhou; Xinhao Zhao; Lin Yang; Liying Li (Journal of Molecular Medicine, 2024)

Associations of long-term exposure to low-level PM2.5 and brain disorders in 260,922 middle-aged and older adults - Ne Qiang; Yujia Bao; Yongxuan Li; Na Zhang; Yanqiu Zhou; Xiaobei Deng; Lefei Han; Jinjun Ran (Chemosphere, 2024)

Molecular mechanism of color deepening of ready-to-eat shrimp during storage - Na Li; Xin Fan; Tingjia Chen; Yefan Wang; Zhifeng Tan; Chang Liu; Dayong Zhou; Deyang Li (Food Chemistry, 2024)

A degradable multi-functional packaging based on chitosan/silk fibroin via incorporating cellulose nanocrystals-stabilized cinnamon essential oil pickering emulsion - Jian-Dong Wang; Shi-Liang Yang; Guo-Sheng Liu; Quan Zhou; Li-Na Fu; Qi Gu; Zi-Hui Cai; Su Zhang; Yu-Jie Fu (Food Hydrocolloids, 2024)

Steep oceanic DIC δ13C depth gradient during the Hirnantian Glaciation - Shengchao Yang; Junxuan Fan; Thomas J. Algeo; Graham A. Shields; Ying Zhou; Chao Li; Jitao Chen; Weiqiang Li; Na Li; Jian Cao; Linna Zhang; Zongyuan Sun; et al. (Earth-Science Reviews, 2024)

Root traits and plasticity differences explain complementarity between co-existing species in phosphorus-limited grassland - Hui Ji; Na Zhou; Zed Rengel; Jingying Jing; Hongbo Li (Plant and Soil, 2024)

Two different types of hydrolases co-degrade ochratoxin A in a highly efficient degradation strain Lysobacter sp. CW239 - Xiaojie Fu; Qingru Fei; Xuanjun Zhang; Na Li; Liang Zhang; Yu Zhou (Journal of Hazardous Materials, 2024)

Photochemistry of plateau lake-derived dissolved organic matter: Reactive species generation and effects on 17β-estradiol photodegradation - Huaying Liu; Yi-na Tu; Yajie Lei; Die Zhou; Qilin Zhao; Yingjie Li; Wenjiao Pan (Journal of Hazardous Materials, 2024)

Water-soluble metal-organic cages crosslinked injectable hydrogel for multi-modal synergistic therapy - Wen-Zhen Li; Xiao-Fan Rong; Yu Wang; Jia-Wen Xiong; Na Zhou; Zi-Xin Wang; Xi-Jia Fang; Wenjing Wang; Yi Liu; Xiao-Qiang Wang (Chemical Engineering Journal, 2024)

Preparation of co-doped biochar to improve electron transfer and modulate 1O2 generation: Unraveling the radical-unradical mechanism - Jingyang Zhang; Shuyi Yang; Kexin Zhou; Jiaqi Zhao; Junbo Wang; Na Li; Yuanfei Wang; Yun Li; Tao E (Chemical Engineering Journal, 2024)

Effect of Lactobacillus fermentation on the structural feature, physicochemical property, and bioactivity of plant and fungal polysaccharides: A review - Zichao Wang; Yi Zheng; Xueyan Zhou; Xueqin Wang; Xirui Liu; Qiong Wang; Renyong Zhao; Minjie Gao; Zhitao Li; Yingjie Feng; Yongming Xu; Na Li; et al. (Trends in Food Science & Technology, 2024)

Overall and geographic pattern of incidence, fatality and mortality of sepsis among hospitalized non-child cancer patients in China: A nationwide cross-sectional study - Bin Lu; Yang Xu; Na Li; Yueyang Zhou; Xudong Ma; Yan Chen; Run Dong; Xiang Zhou; Min Dai; Hongda Chen; Li Weng; Bin Du (Science Bulletin, 2024)

Short-term electrochemical stimulation induces sustained enhancement of extracellular pollutant degradation in anaerobic granular sludge - Liang Cheng; Shu-Na Li; Xiang-Tong Zhou; Xiang Xiao; Yang-Yang Yu (Journal of Water Process Engineering, 2024)

Carbon nanotube incorporated quaternized lignin-based loose nanofiltration membrane toward dye/salt separation - Zhenyu He; Na Zhang; Li Zhao; Zhenghua Li; Wanling Cui; Yuangang Zhu; Yi Wang; Huining Deng; Chengrun Si; Wen Bo; Jie Zhou; Shicai Xu; et al. (Journal of Environmental Chemical Engineering, 2024)

Antibiotic resistance, biofilm formation, and molecular epidemiology of Staphylococcus aureus in a tertiary hospital in Xiangyang, China - Yitong Tang; Na Xiao; JiuMing Zou; Yuling Mei; Yue Yuan; Menghuan Wang; Zezhou Wang; Yunjuan Zhou; Yiyuan Chen; Shichao Li (Brazilian Journal of Microbiology, 2024)

Regional variations in management and outcomes of patients with acute coronary syndrome in China: Evidence from the National Chest Pain Center Program - Shuduo Zhou; Yan Zhang; Xuejie Dong; Junxiong Ma; Na Li; Hong Shi; Sidney C. Smith; Yinzi Jin; Ming Xu; Dingcheng Xiang; Zhi-Jie Zheng; Yong Huo (Science Bulletin, 2024)

Luminescence chronology of the Xiachuan Paleolithic site in Shanxi Province, northern China: A comparison between OSL and post-IR IRSL ages - Na Zhao; Jianping Wang; Liping Zhou; Sanling Li; Haiyun Ren; Shuisheng Du (Quaternary International, 2024)

Effects of calcium chloride on the gelling and digestive characteristics of myofibrillar protein in Litopenaeus vannamei - Kexin Zhang; Yefan Wang; Xin Fan; Na Li; Zhifeng Tan; Huilin Liu; Xiaoyang Liu; Dayong Zhou; Deyang Li (Food Chemistry, 2024)

Superior room-temperature efficacy of selective catalytic reduction of NO by CO utilizing metal-modified Fe2O3 catalysts - Yuqing Pan; Na Li; Chenyang Wu; Qulan Zhou; Ke Li; Shuzhou Li (Chemical Engineering Journal, 2024)

Genome constitution and evolution of Elymus atratus (Poaceae: Triticeae) inferred from cytogenetic and phylogenetic analysis - Lu Tan; Dan-Dan Wu; Chang-Bing Zhang; Yi-Ran Cheng; Li-Na Sha; Xing Fan; Hou-Yang Kang; Yi Wang; Hai-Qin Zhang; Marcial Escudero; Yong-Hong Zhou (Genes & Genomics, 2024)

Spatiotemporal characteristics of water exchange between the Andaman Sea and the Bay of Bengal - Yihao Wang; Feng Zhou; Xueming Zhu; Ruijie Ye; Yingyu Peng; Zhentao Hu; Haoran Tian; Na Li (Acta Oceanologica Sinica, 2024)

Spatial-temporal constraints for surface soil moisture mapping using Sentinel-1 and Sentinel-2 data over agricultural regions - ZHOU Ya'nan; WANG Binyao; ZHU Weiwei; FENG Li; HE Qisheng; ZHANG Xin; WU Tianjun; YAN Na'na (Computers and Electronics in Agriculture, 2024)

Achieving zero fouling in the ultrafiltration for secondary water supply systems in the absence of residual chlorine - Huizhi Hu; Fang Xu; Rui Wang; Chu Zhou; Na Li; Senlin Shao (Water Research, 2024)

Long-term organic amendments increase the vulnerability of microbial respiration to environmental changes: Evidence from field and laboratory studies - Chenglong Ye; Na Li; Juan Gui; Mengyi Zhu; Yan Zhou; Daming Li; Kuihu Jiao; Bryan S. Griffiths; Shuijin Hu; Manqiang Liu (Science of The Total Environment, 2024)

Environmentally relevant concentrations of 2,3,7,8-TCDD induced inhibition of multicellular alternative splicing and transcriptional dysregulation - Bilin Zhao; Jiewei Deng; Mei Ma; Na Li; Junlin Zhou; Xinyan Li; Tiangang Luan (Science of The Total Environment, 2024)

A discussion on N-terminal signal peptide removed ADH3 and the hydrolytic activity on ochratoxin A in the published paper by Dai et al. (2023) - Xuanjun Zhang; Na Li; Han Luo; Yu Zhou (Journal of Hazardous Materials, 2024)

Transition-state defect structure: A new strategy for TiO2-based porous materials to enhance photodegradation of pollutants - Jingyang Zhang; Tao E; Ruifeng Zhou; Na Li; Yuanfei Wang; Yun Li; Shuyi Yang (Journal of Environmental Management, 2024)

Facile construction of superhydrophobic/superoleophilic melamine sponges with durability and antifouling for selective oil absorption and effective oil/water separation - Ye Li; Xin Li; Le Xu; Yihang Yang; Zhaojian Gao; Yingmei Zhou; Na Zhang; Hongri Wan; Teng Chen (Journal of Environmental Chemical Engineering, 2024)

Molecular mechanism of efficient degradation of TPM dyes by Serratia species WKD at high temperature - Yi Wei; Xin-Jiao Dong; Gang Li; Huan Wu; Lin-Na Du; Jia-Cheng Zhou; Jun Zhang; Yan-Ping Xiao; Yue-Mei Shang; Hong-Xia Liu (International Biodeterioration & Biodegradation, 2024)

Classification of natural gas hydrate resources: Review, application and prospect - Na Wei; Jun Pei; Haitao Li; Shouwei Zhou; Jinzhou Zhao; Bjørn Kvamme; Richard Banks Coffin; Liehui Zhang; Yao Zhang; Jin Xue (Gas Science and Engineering, 2024)

Effect of konjac glucomannan on gelling and digestive properties of myofibrillar protein in Litopenaeus vannamei based on molecular docking - Deyang Li; Na Li; Yefan Wang; Kexin Zhang; Zhifeng Tan; Huilin Liu; Xiaoyang Liu; Qiong Wu; Dayong Zhou (Food Hydrocolloids, 2024)

Cross-talk between Vimentin and autophagy regulates blood-testis barrier disruption induced by cadmium - Na Chen; Xiaoyan Wan; Mei Wang; Yamin Li; Xiaofei Wang; Ling Zeng; Jinzhao Zhou; Yanwei Zhang; Shun Cheng; Yi Shen (Environmental Pollution, 2024)

Effect of beta-cypermethrin on the reproductive capacity of female mice in advanced age - Qian-Feng Qiao; Li-Qing Wang; De-E. Yu; Na Li; Qiong-Jun Xu; Yong-Jiang Zhou (Environmental Toxicology and Pharmacology, 2024)

Always positive covalent organic nanosheet enabling pH-independent adsorption and removal of Cr(Ⅵ) - Dong-Xiao Cao; Yun-Jie Zhou; Hong-Xin Jiang; Xue-Nan Feng; Xiao-Yang Liu; Wei Li; Jing-Qi Liu; An-Na Tang; De-Ming Kong (Journal of Hazardous Materials, 2024)

Response of the C-fixing bacteria community to precipitation changes and its impact on bacterial necromass accumulation in semiarid grassland - Na Li; Baorong Wang; Yue Zhou; Huijun Li; Zhaolong Zhu; Yanxing Dou; Yimei Huang; Feng Jiao; Shaoshan An (Journal of Environmental Management, 2024)

The green and low-carbon development pathways in the urban and rural building sector in Shaanxi Province, China - Tingting Zhou; Xi Luo; Xiaojun Liu; Xiongxiong Zhai; Yongkai Sun; Guangchuan Liu; Jianghua Liu; Yaru Gao; Daifeng Dang; Na Li; Pingan Feng; Yuan Gao; et al. (Energy and Buildings, 2024)

Removing refractory organic substances from landfill leachate using a nanofiltration membrane bioreactor: Performance and mechanisms - Chu Zhou; Na Li; Wenbin Guo; Rui Wang; Yaohua Yan; Senlin Shao (Chemical Engineering Journal, 2024)

Norepinephrine-induced hydrophilic Pd aerogels with photothermal-boosted multienzyme-like activity for chemodynamic therapy of MRSA infections - Minghui Wang; Na Li; Nanyun Lin; Yingying Wu; Wei Zhou; Ximei Sun; Peixian Wu; Qian Fu; Wenjie Wang; Zheng Liu; Shuiyuan He; Mengyu Zhou; et al. (Chemical Engineering Journal, 2024)

Development of a PEI-coated SWNTs Nanocarrier for efficient delivery of CRISPR/Cas9 in early embryos of Litopenaeus vannamei - Jia L. Men; Yu T. Zhang; Yue B. Pei; Na Li; Jian H. Xiang; Hai L. Zhou (Aquaculture, 2024)

Mechanism of action of marine ecological restoration on ecological, economic, and social benefits—An empirical analysis based on a structural equation model - Na Wang; Jing-Mei Li; Yu-Fei Zhou (Ocean & Coastal Management, 2024)

Evaluation of therapeutic benefits of botulinum toxin for foot dystonia associated with Parkinson's disease - Ping Ni; Ying-ying Xu; Lin-na Wang; Jia-qian Cao; Wei-feng Luo; Qi-lin Zhang; Xiang Li; Xu-ping Zhou; Jing Liu (Toxicon, 2024)

Long-term exposure to the mixture of phthalates induced male reproductive toxicity in rats and the alleviative effects of quercetin - Li-Lan Liu; Jun-Zhe Yue; Zhen-Yu Lu; Ru-Ya Deng; Can-Can Li; Ye-Na Yu; Wen-Jin Zhou; Min Lin; Hai-Tao Gao; Jiaming Liu; Ling-Zi Xia (Toxicology and Applied Pharmacology, 2024)

PLZF protein forms a complex with protein TET1 to target TCF7L2 in undifferentiated spermatogonia - Xiaomin Du; Donghui Yang; Xiuwei Yu; Yudong Wei; Wenbo Chen; Yuanxin Zhai; Fanglin Ma; Mengfei Zhang; Shicheng Wan; Yunxiang Li; Xinchun Yang; Aili Aierken; et al. (Theriogenology, 2024)

Mechanisms and targeted reversion/prevention of hepatic fibrosis caused by the non-hereditary toxicity of benzo(a)pyrene - Xinru Du; Ming Jin; Ruzhi Li; Fei Zhou; Yuanze Sun; Qinliang Mo; Sisi Song; Na Dong; Shuoke Duan; Maoxuan Li; Ming Lu; Chi Zhang; et al. (Science of The Total Environment, 2024)

Effects of environmentally relevant concentrations of niclosamide on lipid metabolism and steroid hormone synthesis in adult female zebrafish - Xianglin Chen; Shangyue Yang; Biran Zhu; Mengyuan Zhang; Na Zheng; Jianghuan Hua; Ruiwen Li; Jian Han; Lihua Yang; Bingsheng Zhou (Science of The Total Environment, 2024)

Recent advances in the color of aquatic products: Evaluation methods, discoloration mechanism, and protection technologies - Kexin Zhang; Na Li; Zonghan Wang; Dingding Feng; Xiaoyang Liu; Dayong Zhou; Deyang Li (Food Chemistry, 2024)

Multiple spatial scales of bacterial and fungal structural and functional traits affect carbon mineralization - Zhiyuan Ma; Shuo Jiao; Kaikai Zheng; Haowei Ni; Dong Li; Na Zhang; Yunfeng Yang; Jizhong Zhou; Bo Sun; Yuting Liang (Molecular Ecology, 2024)
Studying the functional heterogeneity of soil microorganisms at different spatial scales and linking it to soil carbon mineralization is crucial for predicting the response of soil carbon stability to environmental changes and human disturbance. Here, a total of 429 soil samples were collected from typical paddy fields in China, and the bacterial and fungal communities as well as functional genes related to carbon mineralization in the soil were analysed using MiSeq sequencing and GeoChip gene microarray technology. We postulate that CO 2 emissions resulting from bacterial and fungal carbon mineralization are contingent upon their respective carbon consumption strategies, which rely on the regulation of interactions between biodiversity and functional genes. Our results showed that the spatial turnover of the fungal community was 2–4 times that of the bacterial community from hundreds of meters to thousands of kilometres. The effect of spatial scale exerted a greater impact on the composition rather than the functional characteristics of the microbial community. Furthermore, based on the establishment of functional networks at different spatial scales, we observed that both bacteria and fungi within the top 10 taxa associated with carbon mineralization exhibited a prevalence of generalist species at the regional scale. This study emphasizes the significance of spatial scaling patterns in soil bacterial and fungal carbon degradation functions, deepening our understanding of how the relationship between microbial decomposers and soil heterogeneity impacts carbon mineralization and subsequent greenhouse gas emissions.

Antioxidant analysis of flavonoids extracted from Artemisia argyi leaf and their antibacterial activities against food-borne pathogens Escherichia coli and Staphylococcus aureus - Zichao Wang; Xueyan Zhou; He Chang; Zhihan Shu; Haiqin Gou; Yi Zheng; Yanhui Yang; Yahui Yang; Qi Wang; Na Li (Biologia, 2024)

Uptake and distribution of the inorganic components NH4+ and NO3− in PM2.5 by two Chinese conifers - Jiaxing Fang; Shaoning Li; Na Zhao; Xiaotian Xu; Yongbin Zhou; Shaowei Lu (Science of The Total Environment, 2024)

Interfacial Mo-S bond-reinforced hierarchical S-scheme heterostructure of Bi2MoO6@ZnIn2S4 for highly-selective and efficient CO2 photoreduction into CO - Jiale He; Jie Lin; Yu Zhang; Yingfei Hu; Qingling Huang; Guobing Zhou; Wei Li; Jianqiang Hu; Na Hu; Zhen Yang (Chemical Engineering Journal, 2024)

Facile fabrication of regenerable spherical La0.8Ce0.2MnO3 pellet via wet-chemistry molding strategy for elemental mercury removal - Wei Zheng; Xingyue Zhou; Yuanyuan Na; Jianping Yang; Yingchao Hu; Qingjie Guo; Zequn Yang; Wenqi Qu; Lijian Leng; Hailong Li (Chemical Engineering Journal, 2024)

The spatiotemporal variation of land surface heat fluxes in Tibetan Plateau during 2001–2022 - Na Li; Ping Zhao; Changyan Zhou (Atmospheric Research, 2024)

Solution plasma synthesis of Pt-decorated Bi12O17Cl2 photocatalysts for efficient upcycling of plastics - Feiyan Wu; Changming Li; Yibo Dou; Jianchi Zhou; Tao Jiang; Yuechao Yao; Na Yeon Lee; Sung Yul Lim; Claus Hélix-Nielsen; Wenjing Zhang (Science of The Total Environment, 2023)

Association of selenium profile with neutralizing antibody response to inactivated SARS-CoV-2 vaccination - Sikang Gao; Na Ren; Taoping Sun; Qi Nie; Sitian Liu; Xuyang Geng; Yao Deng; Zefang Lin; Yu Liu; Li Zhou (Journal of Trace Elements in Medicine and Biology, 2023)

Improving the gelation and digestive properties of myofibrillar protein in Litopenaeus vannamei by ultra-high pressure - Kexin Zhang; Na Li; Junzhang Li; Yefan Wang; Chang Liu; Yuxin Liu; Xiaoyang Liu; Dayong Zhou; Deyang Li (Food Bioscience, 2023)

Ecytonucleospora hepatopenaei n. gen. et comb. (Microsporidia: Enterocytozoonidae): A redescription of the Enterocytozoon hepatopenaei (Tourtip et al., 2009), a microsporidian infecting the widely cultivated shrimp Penaeus vannamei - Yuan Wang; Jie Chen; Ying Na; Xin-cang Li; Jun-fang Zhou; Wen-hong Fang; Hong-xin Tan (Journal of Invertebrate Pathology, 2023)

T4PPVB-COP composite-driven innovative electrochemiluminescence aptasensor for ultra-sensitive detection of chlorpyrifos - Yanping Li; Qiong Hu; Jihui Zhang; Hong Zhou; Na Wang; Yishan Fang; Bo Cui (Food Chemistry, 2023)

Hydrogeochemical characterization and precursor anomalies of hot springs in the North Tianshan orogen - Zhihua Ding; Xiaocheng Zhou; Chengguo Wang; Jingchao Li; Miao He; Jiao Tian; Kayimu Saimaiernaji; Chengying Zhu; Wei Yan; Rong Ma; Xinyong Li; Na Li; et al. (Applied Geochemistry, 2023)

Stability of exogenous Cadmium in different vineyard soils and its effect on grape seedlings - Ajigul Mamut; Jianquan Huang; Okbagaber Andom; He Zhang; Na Zhang; Hu Zhou; Yizhong Lv; Zhaojun Li (Science of The Total Environment, 2023)

Adsorption mechanism of methylene blue by magnesium salt-modified lignite-based adsorbents - Ruzhan Bai; Yan Feng; Lei Wu; Na Li; Quansheng Liu; Yingyue Teng; Runxia He; Keduan Zhi; Huacong Zhou; Xueyan Qi (Journal of Environmental Management, 2023)

Insight into coal catalytic gasification mechanism of Na or Ca using experiments combined with DFT calculations with carbon black as a novel coal model - Ruzhan Bai; Lufeng Liu; Na Li; Quansheng Liu; Yu Meng; Yingyue Teng; Huacong Zhou; Xing Zhou (Fuel, 2023)

Carboxyl-containing components delineation via feature-based molecular networking: A key to processing conditions of fermented soybean - Yuye Gao; Yu Fu; Na Li; Yuetong Jiang; Xiaojing Liu; Congcong Gao; Lishuang Wang; Jian-Lin Wu; Tingting Zhou (Food Chemistry, 2023)

Preparation of PtNiCo alloy/nitrogen-doped porous carbon composites and their electrocatalytic properties - Na Zhou; Ruijin Zhang; Rui Wang; Yinshi Li (Chemical Engineering Journal, 2023)

A comprehensive analysis of the Bencao (herbal) small RNA Atlas reveals novel RNA therapeutics for treating human diseases - Yinghao Cao; Yexuan Lin; Na Sun; Xinyi Du; Yixin Dong; Song Mei; Xingyu Deng; Xiaobei Li; Shaoting Guo; Kegong Tang; Jiaqi Liu; Xiangyu Qiao; et al. (Science China Life Sciences, 2023)

Effect of environmental factors on expression of staphylococcal enterotoxin genes - Hong-na Li; Zhao-di Kang; Tao Wang; Tao Li; Yan-ge Yang; Wei-e Zhou; Fei Yuan (Environmental Science and Pollution Research, 2023)

BPDE-DNA adduct formation and alterations of mRNA, protein, and DNA methylation of CYP1A1, GSTP1, and GSTM1 induced by benzo[a]pyrene and the intervention of aspirin in mice - Aixiang Liu; Xin Li; Lisha Zhou; Xiaoqing Yan; Na Xia; Zhanfei Song; Jingjing Cao; Zhongsuo Hao; Zhihong Zhang; Ruifeng Liang; Hongmei Zhang (Environmental Science and Pollution Research, 2023)

Environmental hazard reduction and anti-aging enhancement of steel slag powder-asphalt mastic based on TiO2@UiO-67 composites - Yang Lv; Shaopeng Wu; Na Li; Huan Wang; Peide Cui; Haiqin Xu; Yuechao Zhao; Chao Yang; Xinxing Zhou; Serji Amirkhanian (Journal of Cleaner Production, 2023)

Prenatal exposure to PM2.5 and its constituents with children's BMI Z-score in the first three years: A birth cohort study - Shuang Zhou; Tiantian Li; Na Han; Kai Zhang; Yi Zhang; Qin Li; Yuelong Ji; Jue Liu; Hui Wang; Jianlin Hu; Ting Liu; Hein Raat; et al. (Environmental Research, 2023)

The addition of nano zero-valent iron during compost maturation effectively removes intracellular and extracellular antibiotic resistance genes by reducing the abundance of potential host bacteria - Shizheng Zhou; Hualing Li; Zhiyin Wu; Si Li; Zhen Cao; Baohua Ma; Yongde Zou; Na Zhang; Ziyu Liu; Yan Wang; Xindi Liao; Yinbao Wu (Bioresource Technology, 2023)

Integration of eQTL and GWAS analysis uncovers a genetic regulation of natural ionomic variation in Arabidopsis - Chaoqun Xu; Ling-Yu Song; Ying Zhou; Dong-Na Ma; Qian-Su Ding; Ze-Jun Guo; Jing Li; Shi-Wei Song; Lu-Dan Zhang; Hai-Lei Zheng (Plant Cell Reports, 2023)

The association between intermediate-term sulfur dioxide exposure and outpatient visits for Parkinson’s disease: a time-series study in southwestern China - Yuegu Hu; Chunbei Zhou; Chunlei Tan; Jianghong Liu; Xiaolong Huang; Xiaoling Liu; Chunyan Yao; Dawei Li; Qingsong Huang; Na Li; Jinyun Long; Xiukuan Li; et al. (Environmental Science and Pollution Research, 2023)

Interaction of metabolism-related pathway gene variants with bisphenol A exposure on serum lipid profiles - Heng He; Fuwei Zhang; Shuang Zhou; Shanshan Zhang; Lu Wang; Jiaoyuan Li; Qiang Zeng; Ying Zhu; Jianbo Tian; Jiang Chang; Liming Cheng; Qing Lu; et al. (Environmental Toxicology and Pharmacology, 2023)

Dynamic Measurements of Cerebral Blood Flow Responses to Cortical Spreading Depolarization in the Murine Endovascular Perforation Subarachnoid Hemorrhage Model - Jin Yan; Wenlang Li; Chao Zhou; Na Wu; Xiaomin Yang; Qiuling Pan; Tao He; Yue Wu; Zongduo Guo; Yongzhi Xia; Xiaochuan Sun; Chongjie Cheng (Translational Stroke Research, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

Laboratory characterization of soft clay mixed with EPS, lime, fly ash, and sodium silicate - Ping Jiang; Wenqian Zheng; Lin Zhou; Na Li; Wei Wang (Bulletin of Engineering Geology and the Environment, 2023)

Construction of a food-grade gene editing system based on CRISPR-Cas9 and its application in Lactococcus lactis NZ9000 - Yangping Zhou; Fei Song; Hongru Yang; Dongyao Li; Na Zhang; Kunlun Huang; Xiaoyun He; Miaoshu Wang; Hongtao Tian; Chen Li (Biotechnology Letters, 2023)

Expression profiles and bioinformatic analysis of microRNAs in myocardium of diabetic cardiomyopathy mice - Ting Wang; Lingling Yuan; Yanxia Chen; Jing Wang; Na Li; Hong Zhou (Genes & Genomics, 2023)

Enhanced ion recognition through bi-directionally layered spacing regulation of 1D tubular titanate nanofilms - Shiyu Sun; Xin Huang; Jingtao Bi; Na Wang; Ting Wang; Lina Zhou; Li Wang; Shyam Lamichhane; Hongxun Hao (Chemical Engineering Journal, 2023)

Study on the effect of Ce–Cu doping on Mn/γ-Al2O3 catalyst for selective catalytic reduction in NO with NH3 - Wen Nie; Xiao Yan; Fengning Yu; Qiu Bao; Na Li; Weiwei Zhou; Wenjin Niu; Qifan Tian (Environmental Geochemistry and Health, 2023)

Ubiquitinomics revealed disease- and stage-specific patterns relevant for the 3PM approach in human sigmoid colon cancers - Hua Yang; Na Li; Liang Chen; Lei Zhou; Yuanchen Zhou; Jixiang Liu; Wenshuang Jia; Ruofei Chen; Junwen Su; Lamei Yang; Xiaoxia Gong; Xianquan Zhan (EPMA Journal, 2023)

Unexpected association between ambient ozone and adult insomnia outpatient visits: A large-scale hospital-based study - Dawei Li; Lili Yang; Nan Wang; Yuegu Hu; Yumeng Zhou; Ning Du; Na Li; Xiaoling Liu; Chunyan Yao; Na Wu; Ying Xiang; Yafei Li; et al. (Chemosphere, 2023)

Photocatalytic ipso-nitration of bromophenol intermediates on Ag/g-C3N4 - Dong Liang; Xiaoyu Zhang; Yanle Li; Yumiao Zhou; Mengyu Ren; Xiaoyue Zhang; Yongxiang Li; Na Zhu (Sustainable Chemistry and Pharmacy, 2023)

Effect of chitosan modification on the properties of magnetic porous biochar and its adsorption performance towards tetracycline and Cu2+ - Shisuo Fan; Xinru Fan; Shuo Wang; Bin Li; Na Zhou; Huacheng Xu (Sustainable Chemistry and Pharmacy, 2023)

Calcium-dependent activation of CPK12 facilitates its cytoplasm-to-nucleus translocation to potentiate plant hypoxia sensing by phosphorylating ERF-VII transcription factors - Biao Fan; Ke Liao; Lin-Na Wang; Li-Li Shi; Yi Zhang; Ling-Jing Xu; Ying Zhou; Jian-Feng Li; Yue-Qin Chen; Qin-Fang Chen; Shi Xiao (Molecular Plant, 2023)

Modification of the structure and function of myofibrillar protein by structurally relevant natural phenolic compounds - Na Li; Kexin Zhang; Xinghua Dong; Yunpeng Xu; Zhifeng Tan; Geng Cao; Xiaoyang Liu; Dayong Zhou; Deyang Li (Food Bioscience, 2023)

Room-temperature self-healing and recyclable polyurethane elastomers with high strength and superior robustness based on dynamic double-crosslinked structure - Yawen Xu; Shuai Zhou; Zihang Wu; Xinyu Yang; Na Li; Zhihui Qin; Tifeng Jiao (Chemical Engineering Journal, 2023)

Cropland abandonment alleviates soil carbon emissions in the North China Plain - Lingjie Lei; Ying Li; Zhenxing Zhou; Na Li; Cancan Zhao; Qiang Li (Environmental Monitoring and Assessment, 2023)

Measurement and real-time monitoring of marine economic security climate in China - Xuemei Li; Shiwei Zhou; Yufeng Zhao; Na Li; Yuyu Sun (Ocean & Coastal Management, 2023)

Ancylobacter mangrovi sp. nov., a novel endophytic bacterium isolated from mangrove plant - Fei-Na Li; Zhou-Qing Zheng; Ming-Sheng Chen; Xiao-Hui Chen; Li Tuo (Systematic and Applied Microbiology, 2023)

Livestock grazing-exclusion under global warming scenario decreases phosphorus mineralization by changing soil food web structure in a Tibetan alpine meadow - Feng Sun; Ruiying Chang; Akash Tariq; Jordi Sardans; Josep Penuelas; Hui Jiang; Xingmei Zhou; Na Li (Science of The Total Environment, 2023)

FTO-Nrf2 axis regulates bisphenol F-induced leydig cell toxicity in an m6A-YTHDF2-dependent manner - Shi-meng Zhou; Jing-zhi Li; Hong-qiang Chen; Yong Zeng; Wen-bo Yuan; Yu Shi; Na Wang; Jun Fan; Zhe Zhang; Yuanyuan Xu; Jia Cao; Wen-bin Liu (Environmental Pollution, 2023)

Genome-wide association analysis of resistance to frogeye leaf spot China race 7 in soybean based on high-throughput sequencing - Chen Na; Huanran Miao; Haipeng Jiang; Jinglin Ma; Hongliang Liu; Suchen Lv; Jinghang Zhou; Yuming Yang; Yuhang Zhan; Weili Teng; Yonguang Li; Xue Zhao; et al. (Theoretical and Applied Genetics, 2023)

Selection of the appropriate reference genes by quantitative real-time PCR in leopard coral groupers Plectropomus leopardus - Han Zhang; Haoran Yang; Pengsuo Li; Na Zhao; Xiaojuan Chen; Yongcan Zhou; Zhenjie Cao; Yun Sun (Journal of Oceanology and Limnology, 2023)

Comparative Analysis of the Generalized Omega Equation and Generalized Vertical Motion Equation - Baofeng Jiao; Lingkun Ran; Na Li; Ren Cai; Tao Qu; Yushu Zhou (Advances in Atmospheric Sciences, 2023)

Zoning technology for the management of ecological and clean small-watersheds via k-means clustering and entropy-weighted TOPSIS: A case study in Beijing - Xiang Li; Xinmiao Meng; Xiaodong Ji; Jinyi Zhou; Chengxi Pan; Na Gao (Journal of Cleaner Production, 2023)

Highly selective CO2 electrocatalytic reduction on nickel single-atom catalyst in a high-temperature shockwave method - Jiawei Wang; Guoping Xiao; Na Gao; Jing Zhou; Mengna Xie; XianLong Du; Chuanqiang Wu; Shibo Xi; Tao Li; Jian-Qiang Wang (Fuel, 2023)

The role of MAPK/NF-κB-associated microglial activation in T-2 toxin-induced mouse learning and memory impairment - Na Li; Chun-Yan Yao; Jun Diao; Xiao-Ling Liu; En-Jie Tang; Qing-Song Huang; Yu-Meng Zhou; Yue-Gu Hu; Xiu-Kuan Li; Jin-Yun Long; Hua Xiao; Da-Wei Li; et al. (Food and Chemical Toxicology, 2023)

Removal of nitrate nitrogen from wastewater by green synthetic hydrophilic activated carbon supported sulfide modified nanoscale zerovalent Iron: Characterization, performance and mechanism - Shuaibing Fang; Jingxi Zhang; Yifan Niu; Shaohua Ju; Yongwan Gu; Kai Han; Xiaoxi Wan; Na Li; Yu Zhou (Chemical Engineering Journal, 2023)

Enhanced low-temperature behavior of selective catalytic reduction of NOx by CO on Fe-based catalyst with looping oxygen vacancy - Yuqing Pan; Na Li; Ke Li; Shiyuan Ran; Chenyang Wu; Qulan Zhou; Jiyuan Liu; Shuzhou Li (Chemical Engineering Journal, 2023)

Polymorphism of Pradofloxacin: Crystal Structure Analysis, Stability Study, and Phase Transformation Behavior - Wenlei Li; Lina Zhou; Beiqian Tian; Kui Chen; Yaoguang Feng; Ting Wang; Na Wang; Xin Huang; Hongxun Hao (Pharmaceutical Research, 2023)

[Cuproptosis-related immune gene signature predicts clinical benefits from anti-PD-1/PD-L1 therapy in non-small-cell lung cancer - Linfeng Luo; Anlin Li; Sha Fu; Wei Du; Li-Na He; Xuanye Zhang; Yixing Wang; Yixin Zhou; Yang Yunpeng; Zhang Li; Shaodong Hong (Immunologic Research, 2023)

Application of malrstone-based conditioner and plantation of Jerusalem artichoke improved properties of saline-alkaline soil in Inner Mongolia - Yujie Zhou; Tianyun Shao; Guotao Men; Jiahao Chen; Na Li; Xiumei Gao; Xiaohua Long; Zed Rengel; Ming Zhu (Journal of Environmental Management, 2023)

Polarity-extended composition profiling via LC-MS-based metabolomics approaches: A key to functional investigation of Citrus aurantium L - Wen Miao; Xiaojing Liu; Na Li; Xiqing Bian; Yiran Zhao; Jing He; Tingting Zhou; Jian-Lin Wu (Food Chemistry, 2023)

RNA binding protein YTHDF1 mediates bisphenol S-induced Leydig cell damage by regulating the mitochondrial pathway of BCL2 and the expression of CDK2-CyclinE1 - Jing-zhi Li; Shi-meng Zhou; Wen-bo Yuan; Hong-qiang Chen; Yong Zeng; Jun Fan; Zhe Zhang; Na Wang; Jia Cao; Wen-bin Liu (Environmental Pollution, 2023)

Low expression of miR-1929-3p mediates murine cytomegalovirus-induced fibrosis in cardiac fibroblasts via targeting endothelin a receptor/NLRP3 inflammasome pathway - Jiayi Li; Yongjia Wang; LaMei Wang; Yuanyuan Qu; Wei Zhou; Hua Zhong; DongMei Xi; Na Tang; Fang He (In Vitro Cellular & Developmental Biology - Animal, 2023)

Association between maternal short-term exposure to ambient air pollution and the risk of fetal distress: A matched case-control study - Hua Xiao; Chunyan Yao; Zongli Qi; Jianghong Liu; Xiaoling Liu; Yumeng Zhou; Enjie Tang; Yuegu Hu; Yuexu Jiang; Dawei Li; Ning Du; Na Li; et al. (Science of The Total Environment, 2023)

A novel endophytic bacterial strain improves potato storage characteristics by degrading glycoalkaloids and regulating microbiota - Fei Song; Chen Li; Na Zhang; Xiaoyun He; Hongru Yang; Ziru Yan; Yangping Zhou; Hongtao Tian; Kunlun Huang (Postharvest Biology and Technology, 2023)

Isolation and evaluation of antioxidants from Arisaema heterophyllum tubers - Na Sun; Huanhuan Yang; Miao Zhou; Yanyan Hou; Xinru Wu; Wenqian Li; Yifang Zhang; Jinge Sun; Xin Xiong; Jihong Huang; Penghua Shu (Phytochemistry Letters, 2023)

Effects of fine ambient particulate matters on de novo hypertensive disorders of pregnancy and blood pressure before 20 weeks - Zhichao Yuan; Qin Li; Tao Su; Jie Yang; Junjun Chen; Yuanzhou Peng; Shuang Zhou; Heling Bao; Shusheng Luo; Hui Wang; Jue Liu; Na Han; et al. (Environmental Research, 2023)

IFI44L as a novel epigenetic silencing tumor suppressor promotes apoptosis through JAK/STAT1 pathway during lung carcinogenesis - Yong Zeng; Hong-qiang Chen; Zhe Zhang; Jun Fan; Jing-zhi Li; Shi-meng Zhou; Na Wang; Su-peng Yan; Jia Cao; Jin-yi Liu; Zi-yuan Zhou; Wen-bin Liu (Environmental Pollution, 2023)

Retraction Note: Downregulation of long non-coding RNA TUG1 suppresses tumor growth by promoting ubiquitination of MET in diffuse large B-cell lymphoma - Hai Cheng; Zhiling Yan; Xue Wang; Jiang Cao; Wei Chen; Kunming Qi; Dian Zhou; Jieyun Xia; Na Qi; Zhenyu Li; Kailin Xu (Molecular and Cellular Biochemistry, 2023)

TET1 involved in bisphenol A induced TM3 Leydig cell toxicity by regulating Cav3.3 hydroxymethylation - Shi-meng Zhou; Wen-bo Yuan; Jing-zhi Li; Hong-qiang Chen; Yong Zeng; Na Wang; Jun Fan; Zhe Zhang; Yuanyuan Xu; Jia Cao; Wen-bin Liu (Chemosphere, 2023)

Structural evolution of lignite from heterogeneous particles to homogeneous products during ruthenium ion catalytic oxidation depolymerization - Yinling Zhang; Huacong Zhou; Jianxiu Hao; Qiufeng Wang; Na Li; Runxia He; Keduan Zhi; Shukun Le; Quansheng Liu (Fuel, 2023)

Association between ambient carbon monoxide levels and hospitalization costs of patients with myocardial infarction: Potential effect modification by ABO blood group - Qing-Song Huang; Lai-Xin Zhou; Li-Li Yang; Yue-Xu Jiang; Hua Xiao; Da-Wei Li; Yu-Meng Zhou; Yue-Gu Hu; Na Li; Ya-Fei Li; Ai-Ling Ji; Peng Luo; et al. (Environmental Research, 2023)

c-kit+VEGFR-2+ Mesenchymal Stem Cells Differentiate into Cardiovascular Cells and Repair Infarcted Myocardium after Transplantation - Pei Zhou; Shu-na Yu; Hai-feng Zhang; Yong-li Wang; Ping Tao; Yu-zhen Tan; Hai-jie Wang (Stem Cell Reviews and Reports, 2023)
Resent study suggests that c-kit + cells in bone marrow-derived MSCs may differentiate toward cardiamyocytes. However, the properties of c-kit + MSCs remain unclear. This study isolated c-kit + VEGFR-2 + cells from rat bone marrow-derived MSCs, and assessed potential of c-kit + VEGFR-2 + MSCs to differentiate towards cardiovascular cells and their efficiency of repairing the infarcted myocardium after transplantation. Gene expression profile of the cells was analyzed with RNA-sequencing. Potential of differentiation of the cells was determined after induction. Rat models of myocardial infarction were established by ligation of the left anterior descending coronary artery. The cells were treated with hypoxia and serum deprivation for four hours before transplantation. Improvement of cardiac function and repair of the infarcted myocardium were assessed at four weeks after transplantation. Gene expression profile revealed that c-kit + VEGFR-2 + MSCs expressed most smooth muscle-specific and myocardium-specific genes, while expression of endothelium-specific genes was upregulated significantly. After induction with VEGF or TGF-β for two weeks, the cells expressed CD31 and α-SMA respectively. At three weeks, BMP-2-induced cells expressed cTnT. After transplantation of the cells, cardiac function was improved, scar size of the infarcted myocardium was decreased, and angiogenesis and myocardial regeneration were enhanced significantly. Moreover, paracrine in the myocardium was increased after transplantation. These results suggest that c-kit + VEGFR-2 + MSCs have a potential of differentiation towards cardiovascular cells. Transplantation of c-kit + VEGFR-2 + MSCs is effective for repair of the infarcted myocardium. c-kit + VEGFR-2 + MSCs may be a reliable source for cell therapy of ischaemic diseases. Graphical abstract

Does aspirin reduce the incidence, recurrence, and mortality of hepatocellular carcinoma? A GRADE-assessed systematic review and dose–response meta-analysis - Shaodi Ma; Guangbo Qu; Chenyu Sun; Haixia Liu; Yuemeng Jiang; Ning Li; Birong Wu; Juan Gao; Linya Feng; Peng Xie; Weihang Xia; Na Hyun Kim; et al. (European Journal of Clinical Pharmacology, 2023)

Isochrysis sp. cultivation in pilot-scale to concurrently produce sustainable triacylglycerols for human milk fat substitutes and fucoxanthin - Daogui Li; Na Chen; Zhihua Zhou; Cairong Zhong; Jingping Fang; Luqiang Huang; Han Sun; Chengdeng Chi; Youcai Zhou; Yongjin He (Algal Research, 2023)

Genome-wide identification of calcium-dependent protein kinases (CDPKs) in pear (Pyrus bretschneideri Rehd) and characterization of their responses to Venturia nashicola infection - Shaohua Liu; Junhao Li; Na Li; Peng Zhou; Liulin Li (Horticulture, Environment, and Biotechnology, 2022)

Characterization of Chlamydia muridarum TC0668 Protein: Localization, Expression, and Inflammation-Inducing Effects on Host Cell - Na Liu; Xiaofang Li; Hao Chen; Chuan Wang; Wenjing Xiang; Shui Tan; Chenchen Song; Emmanuel Wirekoh Arthur; Asamoah Maxwell; Derrick Annang; Zhou Zhou (Current Microbiology, 2022)

Jiella avicenniae sp. nov., a novel endophytic bacterium isolated from bark of Avicennia marina - Yong Zhang; Fang Liu; Fei-Na Li; Ming-Sheng Chen; Xiao Ma; Zhou-Qing Zheng; Li Tuo (Archives of Microbiology, 2022)

Green surfactant-modified TiO2 nanoparticles doped with La-Cr bimetal for NOx removal - Wen Nie; Weiwei Zhou; Na Li; Yun Hua; Qiu Bao; Jiayi Yan; Mingyue Yuan; Cheng Guo; Fengning Yu; Wenjin Niu; Chengyi Liu (Environmental Science and Pollution Research, 2022)

Chronological deposition record of trace metals in sediment cores from Chaohu Lake, Anhui Province, China - Xin Wang; Na Gao; Yangyang Liang; Fei Liu; Xiuping Hong; Xiujie Zhou; Liqiang Sun; Hui Li; Ting Fang (Environmental Monitoring and Assessment, 2022)

The association between short-term ambient sulfur dioxide exposure and hospitalization costs of ischemic stroke: a hospital-based study in Chongqing, China - En-Jie Tang; Yu-Meng Zhou; Li-Li Yang; Nan Wang; Yue-Xu Jiang; Hua Xiao; Yue-Gu Hu; Da-Wei Li; Na Li; Qing-Song Huang; Ning Du; Ya-Fei Li; et al. (Environmental Science and Pollution Research, 2022)

New polymerized sesquiterpene lactones from Ainsliaea yunnanensis and their activity evaluation - Na Zhou; Jin-Jie Li; Yong Wu; Ze-Yu Wang; Xin Wang; Zhi-Peng Yin; Xin-Peng Wang; Yi-Ran Liu; Xiao-Ya Shang (Natural Product Research, 2022)

Transposon insertions within alleles of BnaFT.A2 are associated with seasonal crop type in rapeseed - Qingdong Jin; Gengdong Gao; Chaocheng Guo; Taihua Yang; Ge Li; Jurong Song; Na Zheng; Shuai Yin; Licong Yi; Zhen Li; Xianhong Ge; Graham J. King; et al. (Theoretical and Applied Genetics, 2022)

Elder people can be more susceptible to the association between short-term ambient air pollution and sleep disorder outpatient visits: a time-series study - Yu-Meng Zhou; Shu-Jie An; Yi Cao; Chen Xu; Xiao-Ling Liu; Chun-Yan Yao; Xiang Li; Na Wu; Cheng-Ying Li; Long Wu; Ya-Fei Li; Ai-Ling Ji; et al. (Environmental Science and Pollution Research, 2022)

Soil causes gut microbiota to flourish and total serum IgE levels to decrease in mice - Dongrui Zhou; Na Li; Fan Yang; Honglin Zhang; Zhimao Bai; Yangyang Dong; Mengjie Li; Wenyong Zhu; Zhongjie Fei; Pengfeng Xiao; Xiao Sun; Zuhong Lu (Environmental Microbiology, 2022)
Summary Traditional farm environments induce protection from allergic diseases. In this study, farm environmental factors were classified into three categories, environmental microbes, soil, and organic matter. To explore the impact of soil and environmental microorganisms on gut microbiota and immune function, mice were fed sterilized soil and inhaling microbes, soil microbes, or non‐sterilized soil. Metagenomic sequencing results showed the intake of sterile soil, that is, inhaling a small amount of soil microbes in the air increased gut microbial diversity and the abundance of type III secretion system (T3SS) genes, and decreased serum immune IgE levels induced by 2‐4‐dinitrofluorobenzene (DNFB). The intake of soil microbes increased the abundance of genes involved in the metabolism of short‐chain fatty acids and amino acid biosynthesis. Meanwhile, the intake of soil increased gut microbial diversity, the abundance of T3SS genes and related infectious elements, and genes associated with the metabolism of short‐chain fatty acids and amino acid biosynthesis, and decreased serum IgE levels. Therefore, soil may be useful as a potential ‘prebiotic’ promoting the reproduction and growth of some intestinal microorganisms that harbour bacterial secretion system genes, especially those of T3SS, whose abundance was positively and significantly correlated with innate immune function of mice.

Evaluating the Response of a Tunnel Subjected to Strike-Slip Fault Rupture in Conjunction with Model Test and Hybrid Discrete–Continuous Numerical Modeling - Cui Zhen; Li Jian-he; Fu Xing-wei; Sheng Qian; Zhou Guang-xin; Ma Ya-li-na; Wang Tian-qiang (Rock Mechanics and Rock Engineering, 2022)

Anti-inflammatory and antioxidant activities of chemical constituents from the flower buds of Buddleja officinalis - Fei-Bing Huang; Na Liang; Nusrat Hussain; Xu-Dong Zhou; Muhammad Ismail; Qing-Ling Xie; Huang-He Yu; Yu-Qing Jian; Cai-Yun Peng; Bin Li; Bin Liu; Sheng-Huang Chen; et al. (Natural Product Research, 2022)

Secoiridoid glycosides from the fruits of Cornus officinalis - Xin Wang; Xiang-Jian Zhong; Na Zhou; Lin-Lin Ji; Jin-Jie Li; Ning Cai; Qing-Bo Wang; Peng-Cheng Lin; Xiao-Ya Shang (Natural Product Research, 2022)

Associations of CXCL12 polymorphisms with clinicopathological features in breast cancer: a case-control study - Shuai Lin; Yi Zheng; Meng Wang; Linghui Zhou; Yuyao Zhu; Yujiao Deng; Ying Wu; Dai Zhang; Na Li; Huafeng Kang; Zhijun Dai (Molecular Biology Reports, 2022)
Background Previous studies suggested that CXCL12 was involved in the development, metastasis, and invasion of breast cancer, and genetic variants were associated with the diagnosis and prognosis of patients with breast cancer. The present study was aimed to assess the relationships between CXCL12 polymorphisms (rs1801157, rs2297630, and rs2839693) and susceptibility and clinicopathological features of breast cancer. Methods A case-control study was conducted in 434 breast cancer patients and 450 health controls. Student t -test and chi-square test were used to analyze the differences of age distribution and genotype frequencies between the two groups. Correlations between polymorphisms and clinical parameters were also assessed by chi-square test. The potential effects of the three polymorphisms on CXCL12 were investigated by the public database. Results A statistical association was found between CXCL12 rs1801157 polymorphism and breast cancer risk, possibility of metastasis, and estrogen receptor status. Patients with rs2839693 C/T or C/T-T/T genotypes were more likely to be progesterone receptor-negative. However, no associations of rs2297630 polymorphism with breast cancer risk or any clinicopathological characteristics were observed. In addition, rs2297630 affected the splicing quantitative trait loci of CXCL12 in the subcutaneous fat, rs2839693 polymorphism affected the splicing quantitative trait loci of CXCL12 in the human breast mammary tissues. Conclusions Those results indicated that CXCL12 polymorphisms might be potential diagnostic indicators, and more investigation is needed in the future.

Improving rural women’s health in China: cooking with clean energy - Na Li; Guanglai Zhang; Liguo Zhang; Yingheng Zhou; Ning Zhang (Environmental Science and Pollution Research, 2022)

Identification of A-to-I RNA editing profiles and their clinical relevance in lung adenocarcinoma - Cheng Wang; Mingtao Huang; Congcong Chen; Yuancheng Li; Na Qin; Zijian Ma; Jingyi Fan; Linnan Gong; Hui Zeng; Liu Yang; Xianfeng Xu; Jun Zhou; et al. (Science China Life Sciences, 2022)

Performance and mechanisms of fly ash for graphene oxide removal from aqueous solution - Ping Jiang; Lin Zhou; Wei Wang; Na Li; Fang Zhang (Environmental Science and Pollution Research, 2022)

Effects of different compaction methods on the performance of reinforced earth retaining wall - Lihua Li; Chengbin Fan; Han Yan; Hang Li; Xinlong Zhou; Na Chen; Jie Huang; Zhi Chen (Arabian Journal of Geosciences, 2022)

Saikosaponin-d alleviates hepatic fibrosis through regulating GPER1/autophagy signaling - Yirong Chen; Renye Que; Na Zhang; Liubing Lin; Mengen Zhou; Yong Li (Molecular Biology Reports, 2021)
Background Hepatic fibrosis is the final pathway of chronic liver disease characterized by excessive accumulation of extracellular matrix (ECM), which eventually develop into cirrhosis and liver cancer. Emerging studies demonstrated that Saikosaponin-d (SSd) exhibits a protective role in liver fibrosis. However, the mechanism underlying anti-liver fibrosis of SSd in vivo and in vitro remains unclear. Methods and results Transforming growth factor (TGF)-β and carbon tetrachloride (CCl 4 ) were used for creating liver fibrosis model in vitro and in vivo, respectively. The role of SSd in regulating liver fibrosis was assessed through Sirius red and Masson staining, and IHC assay. We found that SSd attenuated remarkably CCl 4 -induced liver fibrosis as evidenced by decreased collagen level, and decreased expression of fibrotic markers Col 1 and α-SMA. Meanwhile, SSd repressed autophagy activation as suggested by decreased BECN1 expression and increased p62 expression. Compared with HSCs from CCl 4 -treated group, the primary HSCs from SSd-treated mice exhibited a marked inactivation of autophagy. Mechanistically, SSd treatment enhanced the expression of GPER1 in primary HSCs and in TGF-β-treated LX-2 cells. GPER1 agonist G1 repressed autophagy activation, whereas GPER1 antagonist G15 activated autophagy and G15 also damaged the function of SSd on suppressing autophagy, leading to subsequent increased levels of fibrotic marker level in LX-2 cells. Conclusions Our findings highlight that SSd alleviates hepatic fibrosis by regulating GPER1/autophagy pathway.

Atorvastatin Pretreatment Ameliorates Mesenchymal Stem Cell Migration through miR-146a/CXCR4 Signaling - Na Li; Xue-Yuan Guo; Jian Zhou; Xian-Liang Yan; Fang-Fang Yu (Tissue Engineering and Regenerative Medicine, 2021)

Study of the mechanical performance of excavation under asymmetrical pressure and reinforcement measures - Wenchao Zhang; Na Wu; Pengjiao Jia; Xiaoqi Zhou; Hong Li; Guoguang Wang (Arabian Journal of Geosciences, 2021)

Genome-wide association analysis for yield-related traits at the R6 stage in a Chinese soybean mini core collection - Xiangnan Li; Yang Zhou; Yuanpeng Bu; Xinfang Wang; Yumei Zhang; Na Guo; Jinming Zhao; Han Xing (Genes & Genomics, 2021)

B7-H3, Negatively Regulated by miR-128, Promotes Colorectal Cancer Cell Proliferation and Migration - Xiaomao Hu; Minxian Xu; Yangzhi Hu; Na Li; Lei Zhou (Cell Biochemistry and Biophysics, 2021)

Diversity of Endophytic Bacteria in Cardamine hupingshanensis and Potential of Culturable Selenium-Resistant Endophytes to Enhance Seed Germination Under Selenate Stress - Qi Li; Shoubiao Zhou; Na Liu (Current Microbiology, 2021)

Nitrogen form and ratio impact phenolic accumulation and relative gene expression in Cyclocarya paliurus - Jian Qin; Xiliang Yue; Yan Ling; Yongsheng Zhou; Na Li; Xulan Shang; Shengzuo Fang (Trees, 2021)

Neighboring tree species alter uptake of NH4+ and NO3− by Chinese fir - Jing Zhou; Qianru Li; Min Liu; Xiaoqi Zhou; Minghua Song; Na Qiao; Huimin Wang; Xingliang Xu (Trees, 2021)

PARP1 rs1136410 C/C genotype associated with an increased risk of esophageal cancer in smokers - Rongmiao Zhou; Yan Li; Na Wang; Chaoxu Niu; Xi Huang; Shiru Cao; Xiangran Huo (Molecular Biology Reports, 2021)

Divalent tranylcypromine derivative as lysine-specific demethylase 1 inhibitor - Yin Sun; Na Li; Mingbo Su; Xiaowen Wang; Dongmei Zhao; Bing Xiong; Yubo Zhou; Tongchao Liu; Yue-Lei Chen (Medicinal Chemistry Research, 2021)

NLRP3 inflammasome priming and activation in cholestatic liver injury via the sphingosine 1-phosphate/S1P receptor 2/Gα(12/13)/MAPK signaling pathway - Lei Hou; Zhi Zhang; Le Yang; Na Chang; Xinhao Zhao; Xuan Zhou; Lin Yang; Liying Li (Journal of Molecular Medicine, 2021)

Image-Forming Visual Basis of Empathy for Pain in Mice - Kai-Wen Geng; Rui Du; Na Wei; Chun-Li Li; Yan Wang; Wei Sun; Tao Chen; Dong-Yu Wei; Yang Yu; Ting He; Wen-Jun Luo; Rui-Rui Wang; et al. (Neuroscience Bulletin, 2020)

AMPK Ameliorates Tau Acetylation and Memory Impairment Through Sirt1 - Lin Wang; Fang-Xiao Shi; Na Li; Yun Cao; Ying Lei; Jian-Zhi Wang; Qing Tian; Xin-Wen Zhou (Molecular Neurobiology, 2020)

SUMOylation of Pdia3 exacerbates proinsulin misfolding and ER stress in pancreatic beta cells - Na Li; Xi Luo; Qilin Yu; Ping Yang; Zhishui Chen; Xinqiang Wang; Jipin Jiang; Jing Xu; Quan Gong; Decio L. Eizirik; Zhiguang Zhou; Jiajun Zhao; et al. (Journal of Molecular Medicine, 2020)

Strength properties of nano-MgO and cement stabilized coastal silty clay subjected to sulfuric acid attack - Wei Wang; Yuan Li; Kai Yao; Na Li; Aizhao Zhou; Chen Zhang (Marine Georesources & Geotechnology, 2020)

A fundamental theorem for eco-environmental surface modelling and its applications - Tianxiang Yue; Na Zhao; Yu Liu; Yifu Wang; Bin Zhang; Zhengping Du; Zemeng Fan; Wenjiao Shi; Chuanfa Chen; Mingwei Zhao; Dunjiang Song; Shihai Wang; et al. (Science China Earth Sciences, 2020)

Upregulation of AMPK Ameliorates Alzheimer’s Disease-Like Tau Pathology and Memory Impairment - Lin Wang; Na Li; Fang-Xiao Shi; Wei-Qi Xu; Yun Cao; Ying Lei; Jian-Zhi Wang; Qing Tian; Xin-Wen Zhou (Molecular Neurobiology, 2020)

Isolation and identification of two new strains of mammalian orthoreovirus from Chinese tree shrews - Xiaofei Li; Xiaomei Sun; Caixia Lu; Dexuan Kuang; Yuanyuan Han; Wenguang Wang; Pinfen Tong; Na Li; Jingxian Zhou; Jiejie Dai (Archives of Virology, 2020)

Germplasms, genetics and genomics for better control of disastrous wheat Fusarium head blight - Zhengqiang Ma; Quan Xie; Guoqiang Li; Haiyan Jia; Jiyang Zhou; Zhongxin Kong; Na Li; Yang Yuan (Theoretical and Applied Genetics, 2020)

The Potential Role of PKA/CREB Signaling Pathway Concerned with Gastrodin Administration on Methamphetamine-Induced Conditioned Place Preference Rats and SH-SY5Y Cell Line - Gen-Meng Yang; Lu Li; Feng-Lin Xue; Chen-Li Ma; Xiao-Feng Zeng; Yong-Na Zhao; Dong-Xian Zhang; Yang Yu; Qian-Wen Yan; Yi-Qing Zhou; Shi-Jun Hong; Li-Hua Li (Neurotoxicity Research, 2020)

Transcriptomic Analyses of Chilling Stress Responsiveness in Leaves of Tobacco (Nicotiana tabacum) Seedlings - Peilu Zhou; Rayyan Khan; Qiyao Li; Guangliang Liu; Na Xu; Yinju Yang; Yi Wang; Shusheng Wang; Aiguo Chen (Plant Molecular Biology Reporter, 2020)

(±)-Quassidine K, a pair of cytotoxic bis- β -carboline alkaloid enantiomers from Picrasma quassioides - Xin-Ming Guo; Fei Li; Fang-Fang Zheng; Na-Na Gong; Yan Li; Wen-Zhou Feng; Lin Tian (Natural Product Research, 2020)

Effect of nano-MgO on mechanical performance of cement stabilized silty clay - Kai Yao; Dongliang An; Wei Wang; Na Li; Chen Zhang; Aizhao Zhou (Marine Georesources & Geotechnology, 2020)

Transient Receptor Potential Ankyrin 1 Contributes to Lysophosphatidylcholine-Induced Intracellular Calcium Regulation and THP-1-Derived Macrophage Activation - Chao Tian; Rongqi Huang; Feng Tang; Zuoxian Lin; Na Cheng; Xiaobo Han; Shuai Li; Peng Zhou; Sihao Deng; Hualin Huang; Huifang Zhao; Junjie Xu; et al. (The Journal of Membrane Biology, 2020)

Hirsutella sinensis inhibits NLRP3 inflammasome activation to block aristolochic acid-induced renal tubular epithelial cell transdifferentiation - Min Yu; Yu-lin Man; Meng-hua Chen; Li-hua Wu; Yi Zhou; Xiao-ling Zhou; Na Chen; Rui Ma; Li-na Sun (Human Cell, 2020)

Formation mechanism and mixing behavior of Nanyang thermal spring, Xingshan County of Hubei Province, central China - Na Li; Hong Zhou; Zhang Wen; Hamza Jakada (Hydrogeology Journal, 2019)

RETRACTED ARTICLE: Downregulation of long non-coding RNA TUG1 suppresses tumor growth by promoting ubiquitination of MET in diffuse large B-cell lymphoma - Hai Cheng; Zhiling Yan; Xue Wang; Jiang Cao; Wei Chen; Kunming Qi; Dian Zhou; Jieyun Xia; Na Qi; Zhenyu Li; Kailin Xu (Molecular and Cellular Biochemistry, 2019)

A random forest model for inflow prediction at wastewater treatment plants - Pengxiao Zhou; Zhong Li; Spencer Snowling; Brian W. Baetz; Dain Na; Gavin Boyd (Stochastic Environmental Research and Risk Assessment, 2019)

Upper and Lower Bound Interval Forecasting Methodology Based on Ideal Boundary and Multiple Linear Regression Models - Wei Li; Jianzhong Zhou; Lu Chen; Kuaile Feng; Hairong Zhang; Changqing Meng; Na Sun (Water Resources Management, 2019)

Impact of surfactant and dissolved organic matter on uptake of atrazine in maize and its mobility in soil - Bing Bing Tian; Jing Hua Zhou; Fei Xie; Qian Nan Guo; Ai Ping Zhang; Xin Qiang Wang; Qian Qian Yu; Na Li; Hong Yang (Journal of Soils and Sediments, 2019)

Genomic Selection Using BayesCπ and GBLUP for Resistance Against Edwardsiella tarda in Japanese Flounder (Paralichthys olivaceus) - Yang Liu; Sheng Lu; Feng Liu; Changwei Shao; Qian Zhou; Na Wang; Yangzhen Li; Yingming Yang; Yingping Zhang; Hejun Sun; Weiwei Zheng; Songlin Chen (Marine Biotechnology, 2018)

Overexpression of Chalcone Isomerase (CHI) Increases Resistance Against Phytophthora sojae in Soybean - Yang Zhou; Jian-li Huang; Xiao-li Zhang; Long-ming Zhu; Xin-fang Wang; Na Guo; Jin-ming Zhao; Han Xing (Journal of Plant Biology, 2018)

Conflicting meal recommendations for oral oncology drugs: pose risks to patient care? - Guo Yu; Dan-Na Wu; Yan Gong; Guo-Fu Li; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2018)

Early diagnosis of acute kidney injury in aged patients undergoing percutaneous coronary intervention - Hong-hua Ye; Gen Shen; Qun Luo; Fang-fang Zhou; Xiao-ling Xie; Chun-yan Wang; Li-na Han (Journal of Zhejiang University-SCIENCE B, 2018)

Available forms of nutrients and heavy metals control the distribution of microbial phospholipid fatty acids in sediments of the Three Gorges Reservoir, China - Hongyang Sun; Yanhong Wu; Haijian Bing; Jun Zhou; Na Li (Environmental Science and Pollution Research, 2018)

Gender-Related Hippocampal Proteomics Study from Young Rats After Chronic Unpredicted Mild Stress Exposure - Lin-Na Ning; Teng Zhang; Jiang Chu; Na Qu; Li Lin; Ying-Yan Fang; Yan Shi; Peng Zeng; Er-Li Cai; Xiao-Ming Wang; Qun Wang; You-Ming Lu; et al. (Molecular Neurobiology, 2018)

Addition of large amount of municipal sewage sludge as raw material in cement clinker production - Minrui Huang; Huajun Feng; Na Li; Dongsheng Shen; Yuyang Zhou; Yufeng Jia (Environmental Science and Pollution Research, 2017)

Complete mitochondrial genome of the Pleuronichthys lighti (Pleuronectiformes, Pleuronectidae) with phylogenetic consideration - Yaoxuan Song; Na Song; Yongdong Zhou; Pengfei Li; Shujiang Zhao; Tianxiang Gao (Genes & Genomics, 2017)

Macroinvertebrate distribution and aquatic ecology in the Ruoergai (Zoige) Wetland, the Yellow River source region - Na Zhao; Mengzhen Xu; Zhiwei Li; Zhaoyin Wang; Hanmi Zhou (Frontiers of Earth Science, 2017)

Resveratrol Inhibits Diabetic-Induced Müller Cells Apoptosis through MicroRNA-29b/Specificity Protein 1 Pathway - Kaihong Zeng; Yuan Wang; Na Yang; Duozi Wang; Suping Li; Jian Ming; Jing Wang; Xuemei Yu; Yi Song; Xue Zhou; Bo Deng; Xiaona Wu; et al. (Molecular Neurobiology, 2017)

Biosynthesis of staphylococcal enterotoxin A by genetic engineering technology and determination of staphylococcal enterotoxin A in water by HPLC-ESI-TOF - Hong-na Li; Fei Yuan; Yun-jing Luo; Jian-feng Wang; Chuan-bin Zhang; Wei-e Zhou; Zhi-qin Ren; Wen-jie Wu; Feng Zhang (Environmental Science and Pollution Research, 2017)

A novel Enterovirus 96 circulating in China causes hand, foot, and mouth disease - Yi Xu; Yisuo Sun; Jinmin Ma; Shuru Zhou; Wei Fang; Jiawei Ye; Limei Tan; Jingkai Ji; Dan Luo; Liqiang Li; Jiandong Li; Chunxiao Fang; et al. (Virus Genes, 2017)

The Adsorption Behavior of Pb2+ and Cd2+ in the Treated Black Soils with Different Freeze-Thaw Frequencies - Xu Wang; Yueming Li; Na Mao; Yanqiu Zhou; Ping Guo (Water, Air, & Soil Pollution, 2017)

A CRISPR/Cas9 toolkit for efficient targeted base editing to induce genetic variations in rice - Bin Ren; Fang Yan; Yongjie Kuang; Na Li; Dawei Zhang; Honghui Lin; Huanbin Zhou (Science China Life Sciences, 2017)

A Point Mutation in SCN1A 5′ Genomic Region Decreases the Promoter Activity and Is Associated with Mild Epilepsy and Seizure Aggravation Induced by Antiepileptic Drug - Qu-Wen Gao; Li-Dong Hua; Jie Wang; Cui-Xia Fan; Wei-Yi Deng; Bin Li; Wen-Jun Bian; Chuan-Xing Shao; Na He; Peng Zhou; Wei-Ping Liao; Yi-Wu Shi (Molecular Neurobiology, 2017)

The Brain NO Levels and NOS Activities Ascended in the Early and Middle Stages and Descended in the Terminal Stage in Scrapie-Infected Animal Models - Li-Na Chen; Jing Sun; Xiao-Dong Yang; Kang Xiao; Yan Lv; Bao-Yun Zhang; Wei Zhou; Cao Chen; Chen Gao; Qi Shi; Xiao-Ping Dong (Molecular Neurobiology, 2017)

Novel compound heterozygous mutations in ZAP70 in a Chinese patient with leaky severe combined immunodeficiency disorder - Qing Liu; Yan-Ping Wang; Qiao Liu; Qin Zhao; Xue-Mei Chen; Xiu-Hong Xue; Li-Na Zhou; Yuan Ding; Xue-Mei Tang; Xiao-Dong Zhao; Zhi-Yong Zhang (Immunogenetics, 2017)

The bioconcentration ability of heavy metal research for 50 kinds of rice under the same test conditions - Wen-Juan Xie; Lei Che; Guang-Yu Zhou; Li-Na Yang; Min-Yu Hu (Environmental Monitoring and Assessment, 2016)

Different responses of soybean cyst nematode resistance between two RIL populations derived from Peking × 7605 under two ecological sites - YONGCHUN LI; NA GUO; JINMING ZHAO; BIN ZHOU; RAN XU; HUI DING; WEIGUO ZHAO; JUNYI GAI; HAN XING (Journal of Genetics, 2016)

A novel diarylheptanoid-bearing sesquiterpene moiety from the rhizomes of Alpinia officinarum - Na Wei; Zhonglin Zhou; Qing Wei; Yong Wang; Jun Jiang; Junqing Zhang; Lixiang Wu; Shuiping Dai; Youbin Li (Natural Product Research, 2016)

Proteomic Analyses for the Global S-Nitrosylated Proteins in the Brain Tissues of Different Human Prion Diseases - Li-Na Chen; Qi Shi; Bao-Yun Zhang; Xiao-Mei Zhang; Jing Wang; Kang Xiao; Yan Lv; Jing Sun; Xiao-Dong Yang; Cao Chen; Wei Zhou; Jun Han; et al. (Molecular Neurobiology, 2016)

NK cells contribute to persistent airway inflammation and AHR during the later stage of RSV infection in mice - Xiaoru Long; Jun Xie; Keting Zhao; Wei Li; Wei Tang; Sisi Chen; Na Zang; Luo Ren; Yu Deng; Xiaohong Xie; Lijia Wang; Zhou Fu; et al. (Medical Microbiology and Immunology, 2016)

Nutrient removal by Chlorella vulgaris F1068 under cetyltrimethyl ammonium bromide induced hormesis - Qiongzhi Zhou; Feng Li; Fei Ge; Na Liu; Yangduo Kuang (Environmental Science and Pollution Research, 2016)

Double-stranded-RNA-specific adenosine deaminase 1 (ADAR1) is proposed to contribute to the adaptation of equine infectious anemia virus from horses to donkeys - Yan-Dong Tang; Xiang Zhang; Lei Na; Xue-feng Wang; Li-Hua Fu; Chun-Hui Zhu; Xiaojun Wang; Jian-Hua Zhou (Archives of Virology, 2016)

The Levels of Tau Isoforms Containing Exon-2 and Exon-10 Segments Increased in the Cerebrospinal Fluids of the Patients with Sporadic Creutzfeldt-Jakob Disease - Cao Chen; Wei Zhou; Yan Lv; Qi Shi; Jing Wang; Kang Xiao; Li-Na Chen; Bao-Yun Zhang; Xiao-Ping Dong (Molecular Neurobiology, 2016)

Reverse transcription genome exponential amplification reaction assay for rapid and universal detection of human rhinoviruses - Li Guan; Lin-Qing Zhao; Hang-Yu Zhou; Kai Nie; Xin-Na Li; Dan Zhang; Juan Song; Yuan Qian; Xue-Jun Ma (Archives of Virology, 2016)

Wogonoside induces growth inhibition and cell cycle arrest via promoting the expression and binding activity of GATA-1 in chronic myelogenous leukemia cells - Hui Li; Hui Hui; Jingyan Xu; Hao Yang; Xiaoxiao Zhang; Xiao Liu; Yuxin Zhou; Zhiyu Li; Qinglong Guo; Na Lu (Archives of Toxicology, 2016)

A wind tunnel study of sand-cemented bodies on wind erosion intensity and sand transport - Jie Zhou; Jiaqiang Lei; Shengyu Li; Haifeng Wang; Na Sun; Xuexi Ma (Natural Hazards, 2016)

Genome-wide association mapping of glyphosate-resistance in Gossypium hirsutum races - Yuan-Yuan Wang; Zhong-Li Zhou; Xing-Xing Wang; Xiao-Yan Cai; Xiao-Na Li; Chun-Ying Wang; Yu-Hong Wang; Liu Fang; Kun-Bo Wang (Euphytica, 2016)

Effects of Saline Water Irrigation and N Application Rate on NH3 Volatilization and N use Efficiency in a Drip-Irrigated Cotton Field - Guangwei Zhou; Wen Zhang; Lijuan Ma; Huijuan Guo; Wei Min; Qi Li; Na Liao; Zhenan Hou (Water, Air, & Soil Pollution, 2016)

LDL acts as an opsonin enhancing the phagocytosis of group A Streptococcus by monocyte and whole human blood - Lulei Zhou; Ling Liu; Jinli Yang; Yuxin Li; Wencheng Bai; Na Liu; Wenlong Li; Yumin Gao; Liping Xu; Zhi Liu; Runlin Han (Medical Microbiology and Immunology, 2016)

Molecular cloning of HMW glutenin subunits from Roegneria kamoji (Poaceae: Triticeae) - Ying-Xia Lei; Kuai Yu; Yi Wang; Xing Fan; Hou-Yang Kang; Li-Na Sha; Yong-Hong Zhou; Hai-Qin Zhang (Biologia, 2016)

Combination of PPT with LiCl Treatment Prevented Bilateral Ovariectomy-Induced Hippocampal-Dependent Cognition Deficit in Rats - Na Qu; Xiang-Yu Zhou; Li Han; Lei Wang; Jia-Xin Xu; Teng Zhang; Jiang Chu; Qiao Chen; Jian-Zhi Wang; Qi Zhang; Qing Tian (Molecular Neurobiology, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

The SIRT1 inhibitor, nicotinamide, inhibits hepatitis B virus replication in vitro and in vivo - Wan-Yu Li; Ji-Hua Ren; Na-Na Tao; Long-Kuan Ran; Xiang Chen; Hong-Zhong Zhou; Bo Liu; Xiao-Song Li; Ai-Long Huang; Juan Chen (Archives of Virology, 2016)

High prevalence and diversity of viruses of the subfamily Gammaherpesvirinae, family Herpesviridae, in fecal specimens from bats of different species in southern China - Xue-yan Zheng; Min Qiu; Shao-wei Chen; Jian-peng Xiao; Li-zhen Ma; Shan Liu; Jun-hua Zhou; Qiong-hua Zhang; Xing Li; Zhong Chen; Yi Wu; Hui-fang Chen; et al. (Archives of Virology, 2016)

Retraction Note to: SELP genetic polymorphisms may contribute to the pathogenesis of coronary heart disease and myocardial infarction: a meta-analysis - Dong-Hui Zhou; Yong Wang; Wei-Na Hu; Li-Jie Wang; Qi Wang; Miao Chi; Yuan-Zhe Jin (Molecular Biology Reports, 2015)

LYG-202 exerts antitumor effect on PI3K/Akt signaling pathway in human breast cancer cells - Yue Zhao; Xiaoping Wang; Yang Sun; Yuxin Zhou; Yuehan Yin; Youxiang Ding; Zhiyu Li; Qinglong Guo; Na Lu (Apoptosis, 2015)

Increased Expression of p-Akt correlates with Chronic Allograft Nephropathy in a Rat Kidney Model - Li-Na Zhou; Ning Wang; Yang Dong; Yiqin Zhang; Hequn Zou; Qingqin Li; Yangling Shi; Ling Chen; Wenying Zhou; Conghui Han; Yuxin Wang (Cell Biochemistry and Biophysics, 2015)

Novel Pyridinium Inner Salt Dye and its Complexes: Synthesis, Crystal Structures and Photophysical Properties - Yong-Hong Zhou; Na-Li Wang; Ti-Fang Miao; Juan-Gang Wang; Zhe-Yu Wang (Journal of Fluorescence, 2015)

Promoter hypermethylation may be an important mechanism of the transcriptional inactivation of ARRDC3, GATA5, and ELP3 in invasive ductal breast carcinoma - Da Wang; Peng-Na Yang; Jin Chen; Xian-Yao Zhou; Qiu-Jun Liu; Hong-Jiang Li; Chang-Long Li (Molecular and Cellular Biochemistry, 2014)

Second order potential vorticity and its potential applications - ShouTing Gao; PengCheng Xu; Na Li; YuShu Zhou (Science China Earth Sciences, 2014)

Molecular characterization of 26 cotton WRKY genes that are expressed differentially in tissues and are induced in seedlings under high salinity and osmotic stress - Li Zhou; Na-Na Wang; Lu Kong; Si-Ying Gong; Yang Li; Xue-Bao Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

The antibacterial activity of phytochemically characterised fractions from Folium Syringae - Zhengyuan Zhou; Na Han; Zhihui Liu; Jinling Wang; Huanzhang Xia; Dezu Miao; Wei Li; Jun Yin (Natural Product Research, 2014)

Biodegradation of 1,4-Dioxane by a Novel Strain and Its Biodegradation Pathway - Huanlin Huang; Dongsheng Shen; Na Li; Dan Shan; Jiali Shentu; YuYang Zhou (Water, Air, & Soil Pollution, 2014)

Influence of ciprofloxacin on microbial community structure and function in soils - Hao Cui; Shu-Ping Wang; Jin Fu; Zhi-Qiang Zhou; Na Zhang; Li Guo (Biology and Fertility of Soils, 2014)

A novel method for the rapid detection of benzo(a)pyrene in liquid milk by dimethyl sulfoxide selectively enhanced synchronous fluorescence spectrometry - Li-Rong Lin; He-Dong Luo; Xiu-Ying Li; Na Li; Na Zhou; Yu-Zhu Jia; Yi-Hong Liu; Yao-Qun Li (Food Additives & Contaminants: Part A, 2014)

Phosphoinositide 3-Kinase Pathway Mediates Early Aldosterone Action on Morphology and Epithelial Sodium Channel in Mammalian Renal Epithelia - Yuan Zhou; Xuewei Chen; Xiao Liu; Hujie Lu; Ying Li; Hui Zhu; Gaihong An; Na Zhang; Jianning Zhang; Qiang Ma; Yanjun Zhang (The Journal of Membrane Biology, 2014)

M3 mAChR-mediated IL-8 expression through PKC/NF-κB signaling pathways - Zu-Peng Xu; Yun Song; Kai Yang; Wei Zhou; Li-Na Hou; Liang Zhu; Hong-Zhuan Chen; Yong-Yao Cui (Inflammation Research, 2014)

Prevalence of human papillomavirus infection in esophageal and cervical cancers in the high incidence area for the two diseases from 2007 to 2009 in Linzhou of Henan Province, Northern China - Hong Yan Liu; Sheng Li Zhou; Jian Wei Ku; Dong Yun Zhang; Bei Li; Xue Na Han; Zong Min Fan; Ji Li Cui; Hong Li Lin; Er Tao Guo; Xi Chen; Yuan Yuan; et al. (Archives of Virology, 2014)

RETRACTED ARTICLE: SELP genetic polymorphisms may contribute to the pathogenesis of coronary heart disease and myocardial infarction: a meta-analysis - Dong-Hui Zhou; Yong Wang; Wei-Na Hu; Li-Jie Wang; Qi Wang; Miao Chi; Yuan-Zhe Jin (Molecular Biology Reports, 2014)

Infection of Prions and Treatment of PrP106–126 Alter the Endogenous Status of Protein 14-3-3 and Trigger the Mitochondrial Apoptosis Possibly via Activating Bax Pathway - Qi Shi; Qin-Qin Song; Peng Sun; Jin Zhang; Juan Song; Li-Na Chen; Kang Xiao; Shao-Bin Wang; Ya-Zhou Zhang; Gong-Qi Li; Lin-Jun Sheng; Bao-Dong Wang; et al. (Molecular Neurobiology, 2014)

Comparative expression analysis of five WRKY genes from Tibetan hulless barley under various abiotic stresses between drought-resistant and sensitive genotype - Huie Li; Qiqiang Guo; Xiaozhong Lan; Qi Zhou; Na Wei (Acta Physiologiae Plantarum, 2014)

Is there a role of TNFR1 in acute lung injury cases associated with extracorporeal circulation? - Yu Zhao; Chong-wei Zhang; Wen-jing Zhou; Jiao Chen; Nan-fu Luo; Li-na Gong; Lei Du; Jing Zhou (Journal of Zhejiang University-SCIENCE B, 2014)

A new species of the genus Trematosphaeria from China - You Zhou; Guoshu Gong; Shirong Zhang; Na Liu; Jingjing Wang; Peili Li; Xiumei Yu (Mycological Progress, 2014)

An integrative bioinformatics pipeline for the genomewide identification of novel porcine microRNA genes - WEI FANG; NA ZHOU; DENGYUN LI; ZHIGANG CHEN; PENGFEI JIANG; DELI ZHANG (Journal of Genetics, 2013)

Structure and dynamics of the bacterial communities in fermentation of the traditional Chinese post-fermented pu-erh tea revealed by 16S rRNA gene clone library - Ming Zhao; Wei Xiao; Yan Ma; Tingting Sun; Wenxia Yuan; Na Tang; Donglian Zhang; Yongxia Wang; Yali Li; Hongjie Zhou; Xiaolong Cui (World Journal of Microbiology and Biotechnology, 2013)

The detection of QTLs controlling bacterial wilt resistance in tobacco (N. tabacum L.) - Yi-liang Qian; Xin-sheng Wang; Da-zhou Wang; Li-na Zhang; Chao-long Zu; Zheng-liang Gao; Hong-jun Zhang; Zhi-yong Wang; Xue-yong Sun; Da-nian Yao (Euphytica, 2013)

Simultaneous adsorption and degradation of Zn2+ and Cu2+ from wastewaters using nanoscale zero-valent iron impregnated with clays - Li-Na Shi; Yan Zhou; Zuliang Chen; Mallavarapu Megharaj; Ravi Naidu (Environmental Science and Pollution Research, 2013)

Separating nitrogen fertilizer and irrigation water application in an alternating furrow irrigation system for maize production - Kun Han; Chunju Zhou; Na Li; John P. Schmidt; Curtis J. Dell; Linquan Wang (Nutrient Cycling in Agroecosystems, 2013)

NBS1 rs1805794G>C polymorphism is associated with decreased risk of acute myeloid leukemia in a Chinese population - Na Li; Yanzhe Xu; Jian Zheng; Lan Jiang; Yonghe You; Hongchun Wu; Wei Li; Depei Wu; Yifeng Zhou (Molecular Biology Reports, 2013)

Construction of multiple shRNAs expression vector that inhibits FUT1 gene expression and production of the transgenic SCNT embryos in vitro - Jian-wen Chen; Yu Zhang; Yuan-liang Zhang; Chao Wei; Xing Liu; Na-ru Zhou; Qing Jia; Yun-sheng Li; Xiao-rong Zhang; Yun-hai Zhang (Molecular Biology Reports, 2013)

The TRIMCyp genotype in four species of macaques in China - Chang-Qing Yu; Lei Na; Xiao-Ling Lv; Jian-Dong Liu; Xiao-Ming Liu; Fang Ji; Yong-Hui Zheng; Hong-Li Du; Xian-Gang Kong; Jian-Hua Zhou (Immunogenetics, 2013)

Functional polymorphisms in PIN1 promoter and esophageal carcinoma susceptibility in Chinese population - Yonghe You; Jieqiong Deng; Jian Zheng; Lan Jiang; Na Li; Hongchun Wu; Wei Li; Jiachun Lu; Yifeng Zhou; Bin Ni (Molecular Biology Reports, 2013)

Involvement of FGF9/16/20 subfamily in female germ cell development of the Nile tilapia, Oreochromis niloticus - Yun-Lv Sun; Sheng Zeng; Kai Ye; Chao Yang; Ming-Hui Li; Bao-Feng Huang; Li-Na Sun; Lin-Yan Zhou; De-Shou Wang (Fish Physiology and Biochemistry, 2012)

Erratum to: Comparative codon usage between the three main viruses in pestivirus genus and their natural susceptible livestock - Jian-hua Zhou; Zong-liang Gao; Jie Zhang; Hao-tai Chen; Zygmunt Pejsak; Li-na Ma; Yao-zhong Ding; Yong-sheng Liu (Virus Genes, 2012)

Molecular and cytological evidences for the natural wheatgrass hybrids occurrence and origin in west China - Jian Zeng; Xing Fan; Hai-Qin Zhang; Li-Na Sha; Hou-Yang Kang; Li Zhang; Rui-Wu Yang; Chun-Bang Ding; Yong-Hong Zhou (Genes & Genomics, 2012)

Identification, fine mapping and characterization of Rht-dp, a recessive wheat dwarfing (reduced height) gene derived from Triticum polonicum - Hou-Yang Kang; Li-Juan Lin; Zhi-Jian Song; Jing-Ya Yuan; Mei-Yu Zhong; Hai-Qin Zhang; Xing Fan; Li-Na Sha; Yi Wang; Li-Li Xu; Jian Zeng; Yong-Hong Zhou (Genes & Genomics, 2012)

Comparative the codon usage between the three main viruses in pestivirus genus and their natural susceptible livestock - Jian-hua Zhou; Zong-liang Gao; Jie Zhang; Hao-tai Chen; Zygmunt Pejsak; Li-na Ma; Yao-zhong Ding; Yong-sheng Liu (Virus Genes, 2012)

Phylogeny and molecular evolution of the DMC1 gene within the StH genome species in Triticeae (Poaceae) - Xiao-Li Wang; Xing Fan; Jian Zeng; Li-Na Sha; Hai-Qin Zhang; Hou-Yang Kang; Rui-Wu Yang; Li Zhang; Chun-Bang Ding; Yong-Hong Zhou (Genes & Genomics, 2012)

−251 T/A polymorphism of the interleukin-8 gene and cancer risk: a HuGE review and meta-analysis based on 42 case–control studies - Na Wang; Rongmiao Zhou; Chunmei Wang; Xiaoqing Guo; Zhifeng Chen; Shan Yang; Yan Li (Molecular Biology Reports, 2012)

Chronic mechanical stress induces mucin5AC expression in human bronchial epithelial cells through ERK dependent pathways - Na Li; Qi Li; Xiang Dong Zhou; Victor P. Kolosov; Juliy M. Perelman (Molecular Biology Reports, 2012)

Construction of a recombinant human FGF1 expression vector for mammary gland-specific expression in human breast cancer cells - Yang Zhou; Linzhu Ren; Jianguo Zhu; Sen Yan; Haijun Wang; Na Song; Li Li; Hongsheng Ouyang; Daxin Pang (Molecular and Cellular Biochemistry, 2011)

Molecular authentication of geo-authentic Scrophularia ningpoensis - Chuan Chen; Li-na Duan; Xiao-long Zhou; Bing-long Chen; Cheng-xin Fu (Journal of Zhejiang University-SCIENCE B, 2011)

P38-Nrf-2 Signaling Pathway of Oxidative Stress in Mice Caused by Nanoparticulate TiO2 - Jue Wang; Na Li; Lei Zheng; Sisi Wang; Ying Wang; Xiaoyang Zhao; Yanmei Duan; Yaling Cui; Min Zhou; Jingwei Cai; Songjie Gong; Han Wang; et al. (Biological Trace Element Research, 2011)

Analysis of codon usage in Newcastle disease virus - Meng Wang; Yong-sheng Liu; Jian-hua Zhou; Hao-tai Chen; Li-na Ma; Yao-zhong Ding; Wen-qian Liu; Yuan-xing Gu; Jie Zhang (Virus Genes, 2011)

Scale issues of wetland classification and mapping using remote sensing images: A case of Honghe National Nature Reserve in Sanjiang Plain, Northeast China - Huili Gong; Cuicui Jiao; Demin Zhou; Na Li (Chinese Geographical Science, 2011)

Molecular characterization and expression analysis of elongation factors 1A and 2 from the Pacific white shrimp, Litopenaeus vannamei - Lei Wang; Yuan Liu; Wei-Na Wang; Wei-Jun Mai; Yu Xin; Jun Zhou; Wen-Yin He; An-Li Wang; Ru-Yong Sun (Molecular Biology Reports, 2011)

Analysis of codon usage in bovine viral diarrhea virus - Meng Wang; Jie Zhang; Jian-hua Zhou; Hao-tai Chen; Li-na Ma; Yao-zhong Ding; Wen-qian Liu; Yong-sheng Liu (Archives of Virology, 2011)

β-catenin signaling involves HGF-enhanced HepG2 scattering through activating MMP-7 transcription - Fei-Yan Pan; Sheng-Zhou Zhang; Na Xu; Fan-Li Meng; Hong-Xia Zhang; Bin Xue; Xiao Han; Chao-Jun Li (Histochemistry and Cell Biology, 2010)

Effects of Manganese Deficiency on Spectral Characteristics and Oxygen Evolution in Maize Chloroplasts - Xiaolan Gong; Ying Wang; Chao Liu; Sisi Wang; Xiaoyang Zhao; Min Zhou; Na Li; Yun Lu; Fashui Hong (Biological Trace Element Research, 2010)

Fluorescent Property of the Gd3+-Doped Terbium Complexes and Crystal Structure of [Tb(TPTZ)(H2O)6]Cl3·3H2O - Yan-Fang Zhao; Yong-Liang Zhao; Feng Bai; Xiao-yan Wei; Yong-sheng Zhou; Mei-na Shan; Huan-huan Li; Rui-jun Ma; Xiao-tao Fu; Yan Du (Journal of Fluorescence, 2010)

Analysis of synonymous codon usage in foot-and-mouth disease virus - Jian-Hua Zhou; Jie Zhang; Hao-Tai Chen; Li-Na Ma; Yong-Sheng Liu (Veterinary Research Communications, 2010)

Association of functional polymorphisms in MMPs genes with gastric cardia adenocarcinoma and esophageal squamous cell carcinoma in high incidence region of North China - Yan Li; Dong-lan Sun; Ya-nan Duan; Xiao-juan Zhang; Na Wang; Rong-miao Zhou; Zhi-feng Chen; Shi-jie Wang (Molecular Biology Reports, 2010)

Cerium Relieves the Inhibition of Nitrogen Metabolism of Spinach Caused by Magnesium Deficiency - Sitao Yin; Yuguan Ze; Chao Liu; Na Li; Min Zhou; Yanmei Duan; Fashui Hong (Biological Trace Element Research, 2009)

The Effects of Lanthanoid on the Structure–Function of Lactate Dehydrogenase from Mice Heart - Na Li; Yanmei Duan; Min Zhou; Chao Liu; Fashui Hong (Biological Trace Element Research, 2009)

Rapid generation of dendritic cell specific transgenic mice by lentiviral vectors - Jinyu Zhang; Liyun Zou; Qin Liu; Jingyi Li; Jingran Zhou; Yong Wang; Na Li; Ting Liu; Hong Wei; Min Wu; Ying Wan; Yuzhang Wu (Transgenic Research, 2009)

Reciprocal regulation between M3 muscarinic acetylcholine receptor and protein kinase C-ε in ventricular myocytes during myocardial ischemia in rats - Peng-zhou Hang; Jing Zhao; Yu-ping Wang; Li-hua Sun; Yong Zhang; Li-li Yang; Na Zhao; Zhi-dan Sun; Yu-ying Mao; Zhi-min Du (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Effects of Cerium on Key Enzymes of Carbon Assimilation of Spinach Under Magnesium Deficiency - Ze Yuguan; Zhou Min; Luo Luyang; Ji Zhe; Liu Chao; Yin Sitao; Duan Yanmei; Li Na; Hong Fashui (Biological Trace Element Research, 2009)

Infectivity and propagation of attenuated infectious bursal disease virus in the chicken B-lymphocyte cell line DT40 - Jun Luo; Gai-Ping Zhang; Jian-Ming Fan; Man Teng; Lei-Ming You; Ling Zhou; Rui-Guang Deng; Xuan-Nian Wang; Yan-Yan Yang; Li Wang; Guang-Xu Xing; Na Cheng (Archives of Virology, 2009)

An investigation on the polymorphisms of two DNA repair genes and susceptibility to ESCC and GCA of high-incidence region in northern China - Na Wang; Xiu-juan Dong; Rong-miao Zhou; Wei Guo; Xiao-juan Zhang; Yan Li (Molecular Biology Reports, 2009)

Genome-wide association scan for stature in Chinese: evidence for ethnic specific loci - Shu-Feng Lei; Tie-Lin Yang; Li-Jun Tan; Xiang-Ding Chen; Yan Guo; Yan-Fang Guo; Liang Zhang; Xiao-Gang Liu; Han Yan; Feng Pan; Zhi-Xin Zhang; Yu-Mei Peng; et al. (Human Genetics, 2009)

Phylogenetic Analysis of Leymus (Poaceae: Triticeae) Inferred from Nuclear rDNA ITS Sequences - Li-na Sha; Rui-wu Yang; Xing Fan; Xiao-li Wang; Yong-hong Zhou (Biochemical Genetics, 2008)

Methylenetetrahydrofolate reductase (MTHFR) C677T and A1298C polymorphisms and the risk of primary Hepatocellular Carcinoma (HCC) in a Chinese population - Li-Na Mu; Wei Cao; Zuo-Feng Zhang; Lin Cai; Qing-Wu Jiang; Nai-Chieh You; Binh Yang Goldstein; Guo-Rong Wei; Chuan-Wei Chen; Qing-Yi Lu; Xue-Fu Zhou; Bao-Guo Ding; et al. (Cancer Causes & Control, 2007)